Phenol hydrodeoxygenation and descriptor based on TM@Mo2C single-atom catalysts - Jiehang Wei; Shouqin Mu; Wenjuan Wang; Yuxin Xu; Mengjia Fu; Yingtao Liu; Xin Wang (Fuel, 2027)

Non-Gaussian fatigue analysis of packaged fruit under random vibration using an improved CEEMDAN hybrid Gaussian decomposition approach - Song-Ping Yang; Jun-Ye He; He-Mu Yu; Tong Ji; Zhi-Wei Wang (Postharvest Biology and Technology, 2026)

Selective adsorption of biodegradable polymaleic acid for regulating the wettability difference at the fine coal–kaolinite interface - Wei Xiao; Yuping Fan; Xianshu Dong; Xiaomin Ma; Yuanpeng Fu; Yanze Mu; Maoqing Yang; Pengcheng Wen; Kangpei Jin; Dehao Li (Minerals Engineering, 2026)

Regulation of casein micelles dissociation by sodium tripolyphosphate to improve gel properties as stabilizers and protein fortifier for high-protein yogurt - Zi-Ying Zhao; Zi-Wei Liu; Bo-Kang Yu; Ying-Chao Qiu; Meng-Jiao Wang; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Landfill leachate as a global PFAS source reservoir: source-strength heterogeneity, compositional transition, and screening-level risk - Xinmiao Chen; Wei Ouyang; Shaoqing Liu; He Zhang; Dijin Mu; Jie Tang; Zhiwei Huang (Water Research, 2026)

Coupled evolution of marine chemocline and nitrogen cycling on continental margins during the Middle Ordovician cooling - Chaogang Fang; Bolin Zhang; Mu Liu; Min Zeng; Haibo Huang; Chengcheng Zhang; Long Teng; Xiangli Wang; Guang-Yi Wei (Global and Planetary Change, 2026)

Transformation of aflatoxins by a thermostable and mediator-independent laccase from Thermincola ferriacetica - Binbin Ouyang; Jiahao Gu; Wei Xu; Alexandra Rojkova; Ivan Zorov; Arkady Sinitsyn; Wanmeng Mu (Food Research International, 2026)

Anion-potential-guided weak-solvation design for polycyanoacrylate gel polymer electrolytes in lithium metal batteries - Peiyang Dong; Zhongpeng Li; Wei Tang; Saihai Lei; Juan Wang; Yu Li; Weihao Zeng; Shichun Mu (Chemical Engineering Journal, 2026)

Unveiling the relationships between process parameters and nitrogen-containing chemicals via machine learning: A strategy for selective production from macroalgae pyrolysis - Mao Chen; Chuan Yuan; Mao Mu; Wei Xiao; Ding Jiang; Zhongmin Pu; Shuang Wang (Bioresource Technology, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Spatiotemporal predictive modeling for coastal phytoplankton based on the Tapnet model: A case study in Zhejiang, China - Yan Wei; Haibin Han; Qinglin Mu; Haodi Zhu; Yueyi Qiao; Shaojian Yang; Chaoyi Yu; Na Wei; Hanyan Luo; Luyuan Zhao; Xuping Zhuo; Yufan Yuan; et al. (Marine Pollution Bulletin, 2026)

MgFe₂O₄/nitrogen‑doped biochar composite microwave absorbers for enhanced catalytic degradation of polycyclic aromatic hydrocarbons in soil - Zheng Dang; Dongmei Wang; Yu Deng; Mu Li; Yan Wei; Xingying Gong; Meikun Fan; Zhengjun Gong (Journal of Environmental Chemical Engineering, 2026)

Static magnetic field coupled with magnetic biochar boosts methane production in sludge anaerobic digestion by activating dual electron transfer mechanisms - Likui Feng; Muzi Li; Kaiyi Zhang; Shuo Liu; Heng Liang; Zhelu Gao; Huizhi Mu; Shufei He; Qingliang Zhao; Liangliang Wei (Journal of Environmental Chemical Engineering, 2026)

Enhancing composite emulsion stability through electrostatic modulation of polysaccharides-whey protein isolate interactions for probiotic encapsulation - Wei-Gang Xin; Yu-Hang Jiang; Yu-Han Dong; Yu-Hang Hou; Mu-Ying Du; Amel Ahmed Ibrahim; Zsolt Zalán; Hua-Yi Suo (Food Chemistry, 2026)

Elucidating the storage destabilization behavior of casein micelle models under direct-steam-infusion UHT processing: insights from plasmin hydrolysis patterns revealed by peptidomics - Mengyuan Guo; Yi Wang; Pengjie Wang; Zhishen Mu; Wentao Qian; Xiaojun Wei; Fazheng Ren; Jie Luo (Food Chemistry, 2026)

Transcriptional and translational optimization for enhancing β-galactosidase expression in bacillus subtilis - Zhuo Cheng; Qiuzi Peng; Jiajun Chen; Li Wan; Dawei Ni; Wei Xu; Penka Petrova; Kaloyan Petrov; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2026)

An eco-friendly integrated short-process of ffor low-grade nickel laterite ore utilization: Glycolic acid leaching kinetics and direct hydro-thermal synthesis of spinel NiFe2O4 anodes - Anlu Wei; Wenning Mu; Xiaolong Bi; Xiang Li; Xuefei Lei; Shaohua Luo (Process Safety and Environmental Protection, 2026)

Study on the mechanism of selective flotation separation of fine coal and kaolinite enhanced by environmentally friendly small-molecule carboxylic acids - Wei Xiao; Yuping Fan; Xiaomin Ma; Jian Niu; Maoqing Yang; Xianshu Dong; Yuanpeng Fu; Zeyu Feng; Pengcheng Wen; Yanze Mu (Minerals Engineering, 2026)

Quantifying potential ground-ice meltwater release and seasonal active-layer water-storage change using decade-long InSAR-derived ground deformation in the Qilian Mountains - Guanjun Wei; Hongyu Zhou; Guangrong Li; Hongwen Mu; Zhigang Du; Yu Li (Journal of Hydrology, 2026)

Airborne microplastics as concentrators of anthropogenic heavy metals: Differentiation of intrinsic additive-derived metals and post-emission enrichment - Wahyu Diah Proborini; Chun-Hsuan Wei; Chun-Hung Ku; Wei-Ting Hsu; Mu-Jean Chen; Hsiu-Chuan Chou; Yu-Cheng Chen (Journal of Hazardous Materials, 2026)

Manganese-amended constructed wetlands coupled with microbial fuel cells significantly enhance methane mitigation: synergistic mechanisms of electrochemical source suppression and manganese-mediated terminal oxidation - Lingyun Mu; Wenjuan Zhai; Xinshan Song; Yunkun Qian; Zhongshuo Xu; Wei Huang (Journal of Environmental Chemical Engineering, 2026)

Land-use change dominates amphibian biodiversity loss, with antagonistic interactions with climate change in the karst region of Guizhou, China - Jing Liu; Shize Li; Gang Wei; Tuo Shen; Lang Mu; Haijun Su (Journal of Environmental Management, 2026)

Permafrost degradation amplifies infrastructure-related inequalities across the Qinghai-Tibet Plateau - Xinlong Du; Chunling Zhang; Yunjie Jia; Yuguo Wei; Jinyue Song; Mei Mu; Xiaoqing Peng; Zongxing Li; Peng Zhang; Lin Liu; Zhuoxuan Xia; Rongkun Liu; et al. (Global Environmental Change, 2026)

Enhanced lactulose production by computer-aided design of cellobiose 2-epimerase - Zhaolin Huang; Wei Xu; Wenli Zhang; Aliaksandr Kastsianevich; Leanida Sapunova; Dawei Ni; Wanmeng Mu (Food Bioscience, 2026)

Catechin-centered metabolic and processing networks in tea flavor formation - Penghui Li; Xiaoyu Mu; Yin Huang; Zhili Ye; Wei-Wei Deng (Current Opinion in Food Science, 2026)

Reaction engineering of a solar chimney-driven honeycomb photocatalytic reactor for outdoor low concentration methane oxidation - Hanbing Xiong; Tingzhen Ming; Yongjia Wu; Liwen Mu; Renaud de Richter; Wenting Lin; Wenyu Li; Chong Peng; Wei Li (Chemical Engineering Journal, 2026)

Nanocarbon catalyzed ethylbenzene oxidative dehydrogenation: Intrinsic activity enhancement via electronic structure modulation with transition metals - Xueya Dai; Miao Guo; Kunru Fan; Ruobing Chen; Mu Niu; Zhifeng Gao; Wei Qi (Chemical Engineering Journal, 2026)

Injectable bioresponsive nanocomposite hydrogels for ROS scavenging and immunomodulation to accelerate diabetic bone repair - Zijian Wang; Wei Jin; Ying Zhou; Jieying Zhang; Xinkun Shen; Caiyun Mu; Maowen Chen (Chemical Engineering Journal, 2026)

TME-activated MXene nanoheterojunctions engineer cancer cells through phototherapy and metabolic interference for enhanced cuproptosis and immunotherapy - Hui Li; Jie Geng; Min Mu; Susu Xiao; Chenqian Feng; Lihua Zhou; Yuanxiang Wang; Wei Yu; Rangrang Fan; Bo Han; Gang Guo (Chemical Engineering Journal, 2026)

A synergistic antifungal buccal composite integrating Aureobasidin A and alkaline modulation for localized treatment of oral candidiasis - Jiaxin Yi; Li Xie; Xueping Shui; Xinzhi Tan; Yandong Mu; Wei Fei; Li Xiao; Weidong Tian; Jun Guo (Chemical Engineering Journal, 2026)

Enhanced levansucrase expression in Bacillus subtilis via regulatory element optimization for high-yield lactosucrose production from sucrose and lactose - Hangbin He; Yang Yang; Qiang Wei; Xiaoyong Liu; Wei Xu; Wenli Zhang; Dawei Ni; Wanmeng Mu (Bioresource Technology, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

A dual colorimetric and fluorescent sensor for non-enzymatic glucose detection via catalytic reaction with o-phenylenediamine mediated by carbon dot-decorated Fe3O4 nanoparticles - Wei-Bin Tseng; Wei-Kai Tsai; Ming-Mu Hsieh; Chi-Yu Lu; Po-Chiao Lin; Wei-Lung Tseng (Analytica Chimica Acta, 2026)

Silicon addition mitigates nitrogen-induced reduction in community stability by increasing species asynchrony, species richness and dominant species stability - Wenhong Zhou; Danghui Xu; Zhengwei Ren; Yuqi Wu; Baiyin Huang; Wenbo Mu; Zhaoliang Song; Wei Mu; Yawen Gui (Acta Oecologica, 2026)

Experimental and Numerical Study on Dynamic Response of PVC Foam Sandwich Beams Under Ice Impact - Kailing Guo; Juncheng Chen; Wei Cai; Shuo Zhou; Mengying Mu (Journal of Marine Science and Engineering, 2026)
This paper mainly investigates the ice-impact resistance of PVC foam sandwich beams for polar ship protective structures through low-velocity impact experiments and nonlinear finite element simulations. An experimentally validated elastic–plastic coupled model, accounting for ice crushing and large structural deformation, was used to examine the effects of core density and face-sheet thickness distribution on the ice-impact response of sandwich beams. Results show that the upper face sheet undergoes local indentation and global bending, the lower face sheet mainly bends globally, and the foam core exhibits local compression and overall bending, while compressive deformation accompanied by ice crushing and spalling occurs at the front part of the ice impactor. Moreover, the effective structural stiffness decreased during plastic loading as local indentation and core compression developed, whereas the unloading stiffness was higher than the effective stiffness during plastic loading. Energy dissipation primarily comes from ice crushing, face-sheet plasticity, and core compression. Increasing core density reduces deflection and core compression but increases peak force. Among the three face-sheet configurations examined at a constant total thickness, the configuration with a thinner upper face sheet and a thicker lower face sheet produced a smaller final deformation of the lower face sheet. This study provides a useful reference for ice-resistant design of sandwich structures in polar ships.

Rapid growth and super air stability of 2D ultrathin superconducting Mo2C crystals - Zhandong Mu; Wen Teng; Wei Guo; Qiang Wang; Chen Chen; Zhibo Liu; Yongfeng Wang; Ning Kang; Chuan Xu; Wencai Ren (Science Bulletin, 2026)

Tuning oxygen vacancy density via facet engineering of TiO2 for selective photocatalytic hydrogenation of 5-hydroxymethylfurfural - Yunlei Zhang; Chaoyue Xu; Xiaotong Mu; Hongke Li; Jian Cao; Maobin Wei; Peng Wang; Yao Chen (Fuel, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Di(2-ethylhexyl) phthalate (DEHP)-induced circadian disruption accelerates aging-related functional declines via oxidative stress and insulin/IGF-1 signaling in Caenorhabditis elegans - Pei-Ling Yen; Wei Lin Chuah; Sin Ni; Tzu-Ting Chang; Mu-En Huang; Vivian Hsiu-Chuan Liao (Environmental Toxicology and Pharmacology, 2026)

A biocompatible catalytic benzyl decaging enables activation of salicylic acid-dependent defense responses in plants - Yanhao Hu; Bo He; Mian Wei; Zhengxi Xiong; Yalin Mu; Ping Chen; Wang Chen; Jiahao Wang; Wei Yan; Yonghao Ye (Chemical Engineering Journal, 2026)

Achieving 9.11 GHz broadband microwave absorption in CeO₂/Sn@C composites via Sn doping and structural modulation - Yecheng Qiu; Hao Ma; Jinhua Du; Wei Li; Xiaolong Wang; Yizhe Tian; Xu Mu; Defang Duan; Yingnan Wang (Chemical Engineering Journal, 2026)

Laser-processed biomimetic hydrogel patches with tunable bio-adhesion, muscle tissue regeneration, and synergistic antibacterial activity - Luxing Wei; Jun Huang; Yingwen Mu; Liuguang Song; Yi Yu; Yuquan Wang; Gexing Peng; Ningji Gong; Jian Shen (Chemical Engineering Journal, 2026)

CNTN6 Modulates Slit-Robo Signaling in Cortical GABAergic Interneuron Migration - Yiliang Xu; Tian Zhao; Dan Zhao; Wei Zhang; Di Mu; Ailing Gui; Junzhi Guo; Kazutada Watanabe; Zhi-Cheng Xiao; Haihong Ye (Neuroscience Bulletin, 2026)

Wind Stress and Wind Disturbance Control Litterfall and Carbon Flux - Chen-Chia Ku; Sin Chen; Cheng-Yu Wu; Chun-Ping Huang; Bing-Mu Hsu; James A. Lutz; Wei-Chun Chao; Cheng-Wei Fan (Ecosystems, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

A precise underwater positioning method by considering TDOMA under fluctuating sea surface - Xukai Mu; Zhenxing Zhao; Wei Gao (Ocean Engineering, 2026)

A multi-source precipitation blending method combining hydrological model-guided precipitation adjustment and double transfer learning-based data merging - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Jiahua Wei; Yuefei Huang; Shenglong Gu; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2026)

Interface behavior of brown soil under freeze-thaw action: Activated the adsorption sites and increased the resistance to desorption for Pb2+ - Wei Yu; Lixin Wang; Xinrui Mu; Xi Chen; Haibo Li (Journal of Environmental Sciences, 2026)

Imidazole-based dual-function molecular structure for a cross-cycle-resistant, long-cycle, membrane-free, anode-free zinc-based battery - Zhenhe Chang; Rui Mu; Wei Zhang; Chaoyue Zhang; Ziang Yao; Haotong Wang; Baohui Wang; Hongjun Wu; Di Gu (Chemical Engineering Journal, 2026)

Corrigendum to “Analysis of impedance mechanisms in aqueous zinc-ion batteries via electrochemical impedance spectroscopy and distribution of relaxation times” [Chem. Eng. J. 537 (2026) 176461] - Zetao Chen; Xiyan Wei; Quanyan Man; Jinpeng Guan; Yongbiao Mu; Lin Zeng (Chemical Engineering Journal, 2026)

Reliability enhancement of PVDF-HFP modified perovskite solar cells under synergistic space-relevant stress conditions - Harini Srikanth Rao; Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Yi-Wen Sung; Gao Chen; Kun-Mu Lee (Chemical Engineering Journal, 2026)

Tidal level seasonally modulates sediment organic carbon in seagrass meadows of tropical lagoon bays - Xiao-Ya Zhang; Hui-Jue Luo; Qian-Wei Li; Mu-Qiu Zhao; Zhen Ni; Yun-Feng Shi; Yin-Liu Wang; Yu-Chao Li (CATENA, 2026)

Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

Suicide attempt risk among patients receiving methylphenidate: a retrospective cohort study - Tai-Long Pan; Li-Chi Chen; Ju-Wei Hsu; Ya-Mei Bai; Shih-Jen Tsai; Tzeng-Ji Chen; Mu-Hong Chen (Psychopharmacology, 2026)
Background Methylphenidate may reduce suicide risk among patients with attention-deficit hyperactivity disorder. Several studies have noted that the association between methylphenidate use and suicidality is weakening. Methods Data were collected from Taiwan’s National Health Insurance Research Database to assess the association between methylphenidate exposure and suicide attempt risk across two exposure periods (main analysis: 2001–2002; duplication analysis: 2004–2005). We compared suicide attempt risk between patients who initiated methylphenidate treatment and those with no recorded psychiatric treatment or methylphenidate exposure during the same period. Results In both the main and duplication analyses, patients receiving methylphenidate exhibited a higher subsequent risk of suicide attempts than unexposed individuals. A duration–response pattern was observed in both cohorts: the hazard ratio of suicide attempts declined with longer cumulative methylphenidate use, from 1.60/1.84 for < 30 days to 1.45/1.65 for ≥ 180 days. Because hazard ratios were closely aligned across 2001–2002 and 2004–2005, the association of methylphenidate with reduced suicide attempt risk did not appear to decrease over time. Discussion Longer use of methylphenidate was associated with a lower risk of subsequent suicide attempts among patients in Taiwan receiving methylphenidate. The beneficial effect of methylphenidate on suicide risk remained consistent over time.

Redefining PHOX2B-Related Neurodevelopmental Disorders as Circuitopathies: A New Paradigm in Autonomic Network Medicine - Zixu Zhang; Shengru Hu; Yaxuan Chen; Ting He; Wei Xie; Mingdao Mu (Neuroscience Bulletin, 2026)

Heteroaggregation with microalgae masks charge-dependent accumulation but amplifies charge-dependent toxicity of nanoplastics in mussels - Fangli Wu; Yuqing Deng; Quanying Wu; Hongxing Chen; Jingli Mu; Yuting Zhang; Wei Meng; Ning Li; Lingtian Xie (Journal of Hazardous Materials, 2026)

Acid-base imbalance electrolytic cell (AB-EC) for efficient treatment of acid mine drainage (AMD): Metal recovery and hydrogen production - Haoyang Song; Zhudi Chen; Jinyuan Jiang; Wei Tan; Zhaocong Ren; Mu Feng; Dongni Shi; Hongke Qin; Lei He; Xiaojun Pan; Kuk Cho (Journal of Environmental Chemical Engineering, 2026)

Multi-omics insights into microbial communities and key flavor formation mechanisms of sweet flour paste under sunroom fermentation mode - Yuanyuan Chen; Qi Qi; Danyu Yan; Xintong Hu; Chi Zhang; Yingchun Mu; Wei Su; Yu Mu (Food Bioscience, 2026)

Comparative assembly mechanisms of microbial communities shape flavor metabolism in high-and low-salt soy sauce fermentation - Danyu Yan; Qi Qi; Xinru Ma; Yanfeng Fu; Linpei Liu; Yingchun Mu; Wei Su; Yu Mu (Food Bioscience, 2026)

Epigenetic impacts of the acaricide flumethrin on honeybees (Apis mellifera) - Xue Wang; Suzhen Qi; Mu Ding; Wei Zhang; Aidi Huang; Changlu Sun; Man Fan; Liming Wu; Miao Wang (Environmental Pollution, 2026)

Analysis of impedance mechanisms in aqueous zinc-ion batteries via electrochemical impedance spectroscopy and distribution of relaxation times - Zetao Chen; Xiyan Wei; Quanyan Man; Jinpeng Guan; Yongbiao Mu; Lin Zeng (Chemical Engineering Journal, 2026)

Speciation and light-absorbing properties of carbonaceous aerosols in a typical industrial city, Taiyuan, China - Ziyong Guo; Chenhui Li; Fengxian Liu; Ying Wei; Jiajie Li; Yanting Qiu; Taomou Zong; Ling Mu; Zhijun Wu; Jiancheng Wang (Atmospheric Environment, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Hyoscyamine Ameliorates Repetitive Behavior in NLG1 and SHANK3 Deficient-Mice - Dandan Lv; Ruining Liu; Xinyu Zhang; Siqi Peng; Wei Xie; Mingdao Mu; An Liu (Neuroscience Bulletin, 2026)

Effects of forest type and elevation on plant and microbial residue carbon concentrations on Kunyu Mountain, China - Wei Zhu; Shiguo Gu; Jinyuan Wang; Tingting Mu; Yanyan Ni; Jun Gao; Mai-He Li (Journal of Soils and Sediments, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Effects of Second-Order Wave Forces on the Extreme Response Estimation of the TLP Offshore Wind Turbine Under Multi-Directional Wind-Wave Loads - Jiahao Mu; Wei Shi; Linyang Cao; Jinghong Shang; Xu Han; Yang Yang; Liang Liu; Guangyuan Cheng (Journal of Marine Science and Engineering, 2026)
As offshore wind energy advances into deeper waters, the dynamic response and safety assessment of tension leg platform (TLP) wind turbines under complex marine conditions have become focal research points. This study investigates a 15 MW TLP wind turbine, acquiring data on motion responses, mooring tensions, and tower-base loads through time-domain analysis, with extreme value estimation conducted using the mean up-crossing rate method. The results indicate that under normal operating conditions, second-order wave forces significantly influence extreme response estimation. At an exceedance probability of 0.01, the second-order sum-frequency force increases the extreme tower base shear by 4.28% and the bending moment by 10.11% compared to the first-order-only case, while the difference-frequency force has a minor effect. Different wind-wave incidence angles cause distinct variations in turbine motion, with head-on incidence exciting the largest wave-frequency responses and lateral incidence producing relatively weaker excitation effects. Furthermore, the coupling effect between incident direction and second-order wave forces further amplifies extreme response risks. Therefore, it is essential to fully assess the prevailing wind-wave directions in the target sea area and consider the effects of second-order wave forces, especially the sum-frequency component, to ensure the long-term safe operation of TLP wind turbines under complex sea conditions.

Integrated toxicity of neonicotinoid Cycloxaprid in the Apis mellifera intestinal system: Oxidative damage, immune activation, and microbial-metabolic interactions - Wei Zhang; Mu Ding; Aidi Huang; Xue Wang; Lihong Qiu; Suzhen Qi (Pesticide Biochemistry and Physiology, 2026)

Enhancement of ultra-high-pressure dewatering of fine coal slurry: Synergistic regulation mechanism of pore interface chemistry by polycarboxylate-CaO - Yuping Fan; Pengcheng Wen; Xiaomin Ma; Xianshu Dong; Ruxia Chen; Maoqing Yang; Wei Xiao; Yanze Mu (Fuel, 2026)

Atomically precise Pd4 cluster on monolayer MoS2 for efficient overall water splitting - Yuxin Xu; Jing Ma; Tao Ma; Jiehang Wei; Mengjia Fu; Wenjuan Wang; Shouqin Mu; Xin Wang; Yingtao Liu (Fuel, 2026)

A thermally induced solid–liquid phase transition strategy enhances pesticide efficacy by improving interfacial behavior - Haojie Gao; Zhongyi Li; Xiaochi Liu; Yujia Kang; Yunyu Tang; Jianfeng Tang; Wei Mu; Daxia Zhang; Xiangyang Li; Feng Liu (Chemical Engineering Journal, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

CoTiO3 immobilized on nickel foam for degradation of levofloxacin via peroxymonosulfate activation: Electron transfer pathways and degradation mechanism - Zhonghua Mu; Peng Cui; Rui Gao; Jikai Liu; Wei Li; Yushu Zhang; Wenqiang Ma; Hairui Li; Shiqi Wu; Shuzheng Zhang; Zhaohui Wang; Lei Yang; et al. (Process Safety and Environmental Protection, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Anaerobic digestion model reconstruction of red mud-Pretreated food waste based on the Metagenomics: Improvement of the high-solid ADM1 incorporating SAO and DIET metabolic pathways - Haoran Mu; Yuying Hu; Shihao Zhang; Xinyi Zhang; Qun Wei (Journal of Environmental Management, 2026)

Construction of highly efficient Bi12O17Cl2/MnWO4 S-scheme heterojunction for photocatalytic degradation of bromophenol blue dye - Pooja Dhiman; Jayati Sharma; Mu. Naushad; Amit Kumar; Chin Wei Lai; Tongtong Wang; Gaurav Sharma (Journal of Environmental Management, 2026)

Combinatorial PPTase screening and systematic metabolic engineering for high-level indigoidine production in Corynebacterium glutamicum - Jiali Zhang; Zeyu Li; Rui Lu; Junsong Xiao; Yingying Zhu; Wei Xu; Wanmeng Mu (Food Bioscience, 2026)

Sustainable and selective gold extraction from electronic waste using conjugated microporous polymer aerogels - Wei Liu; Zhaoqi Zhu; Xicheng Liu; Mengqi Zhao; Rui Jiao; Peng Mu; Hanxue Sun; An Li (Chemical Engineering Journal, 2026)

Tailoring nitric oxide-release hydrogel incorporating MSC-derived exosomes for multimodal therapy of diabetic foot ulcers - Kaijie Zhao; Xuan Tian; Qijian Wei; Yuteng Li; Mingzhuo Zhou; Anhui Mu; Xin Yan; Shilei Ni; Pei Liu (Chemical Engineering Journal, 2026)

Study on the mechanism of mixed biochar enhancing methane production in anaerobic digestion of corn straw - Huilin Zhang; Siyu Zhang; Pujie Wei; Xinyue Zhao; Hong Chang; Zeyan Mu; Xu Zhang; Wei Liu; Xudan Liu; Xiaohong Su; Xin Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Real-time detection and characterization of trunks and upright branches of pear trees for automatic dormant pruning - Hao Sun; Gengchen Wu; Hu Xu; Jiaqi Li; Zhidi Zhou; Shutian Tao; Wei Guo; Kaijie Qi; Hao Yin; Shaoling Zhang; Seishi Ninomiya; Yue Mu (Precision Agriculture, 2026)

Adaptations in ancient oasis woodlands of the hyper-arid Tarim Basin, Northwestern China: charcoal and coprolite analyses - Kangkang Li; Konglan Shao; Ying Yang; Gill Plunkett; Robert Spengler; Bing Xu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Guijin Mu; et al. (Archaeological and Anthropological Sciences, 2026)

A Genetically Defined Thalamic Circuit Encodes Social Touch - Shuyan Geng; Chuanyao Sun; Xing Liu; Zixu Zhang; Shengru Hu; Hao Jiang; Xiaoxia Xue; Tianxiang Xu; Wei Xie; Mingdao Mu (Neuroscience Bulletin, 2026)

Effect of Nitrogen and Maize Straw on Soil Nitrogen Transformation, Farm Profitability, and Wheat Yield: Balancing Productivity and Environmental Sustainability - Siddique Ahmad; Wenjing Song; Yanling Mu; Xiaobin Zhang; Shuping Xiong; Muhammad Arif; Muhammad Amjad; Laiba Urooj; Basit Ullah; Xinming Ma; Yihao Wei (Agricultural Research, 2026)

Metabolic coupling of arsenic, carbon, nitrogen, sulfur and iron in high-salinity groundwater in the Yellow River Delta: Insights from metagenomic analyses - Chuanshun Zhi; Dahai Wang; Baonan He; Guohua Hou; Maosheng Gao; Hui Mu; Ruchun Wei; Xiancang Wu; Jing Bai; Yufei Jiao; Xiaonong Hu (Water Research, 2026)

Research progress in microbial synthesis of D-allulose using metabolically engineered microbes - Junchi Zhu; Like Fan; Jiajun Chen; Wei Xu; Azis Boing Sitanggang; Fina Amreta Laksmi; Junmei Ding; Wanmeng Mu (Trends in Food Science & Technology, 2026)

Performance assessment of canopy gap fraction retrieval using multiple airborne LiDAR instrument configurations - Yi Li; Hao Tang; Shanshan Wei; Donghui Xie; Xihan Mu; Guangjian Yan (Remote Sensing of Environment, 2026)

MeJA regulates plant root growth, development and phosphorus uptake to adapt to low phosphorus stress - Xinxin Wei; Bin Qiao; Siyao Zhang; Junjie Cui; Rongrong Zhang; Tingting Mu; Guobin Zhang (Plant Science, 2026)

Molecular characteristics of water-soluble organic aerosols under pollution conditions in a coal resource-based city revealed by FT-ICR MS: a significant role of sulfur-containing compounds - Chao Zhang; Ziyong Guo; Qingyu Hu; Lin Qi; Yang Chen; Yufeng Zhao; Nan Pei; Wei Sun; Xiaodong Hu; Yuxiang Yang; Fengxian Liu; Ling Mu; et al. (Fuel, 2026)

Oxygen vacancy-engineered electron transfer in bowl-like TiO2 stabilized Au-Pd nanoparticles: Deciphering enhanced strong metal-support interaction for selective 5-hydroxymethylfurfural oxidation - Hongke Li; Changbao Zhou; Yao Chen; Xiaotong Mu; Jian Cao; Maobin Wei; Chen Chen; Yunlei Zhang (Fuel, 2026)

Identification of a novel and thermostable laccase from Bacillus velezensis GLY4 and its application in the biotransformation of aflatoxins - Xin Zhang; Binbin Ouyang; Wei Xu; Hongbin Sun; Wanmeng Mu (Food Bioscience, 2026)

An overview of the physical, chemical and biological strategies for the removal of emerging mycotoxins: Recent advances and future perspectives - Jiayi Yao; Binbin Ouyang; Wei Xu; Yanli Xie; Wanmeng Mu (Food Control, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Hydroxyl-functionalized electrolyte additives for stable low-temperature zinc-ion battery operation - Zhenzhen Kong; Xiyan Wei; Yongbiao Mu; Jinpeng Guan; Zetao Chen; Lin Yang; Liying Wang; Meisheng Han; Lin Zeng (Chemical Engineering Journal, 2026)

Polystyrene microplastics at environmentally realistic concentrations exacerbate diatom blooms caused by phosphorus pollution: Rethinking coastal eutrophication - Xuan Hou; Muhammad Waseem; Muhammad Waseem Boota; Li Mu; Yuanyuan Wei; Xiangang Hu (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Risks and underling mechanisms of sulfoxaflor exposure in honey bees (Apis mellifera): Physiology and behavior impairment - Mu Ding; Xue Wang; Wei Zhang; Aidi Huang; Wenting Zhao; Mai Luo; Liming Wu; Suzhen Qi (Pesticide Biochemistry and Physiology, 2026)

Sustainable N, P co-doped hierarchical porous carbon via coupling phytic acid-melamine assisted hydrothermal carbonization with high temperature activation - Wei Liu; Zhengtong You; Shiqi Qin; Zhipeng Hu; Jiaxin Mu; Zhijun Zhang; Yanjun Xie; Qingwen Wang; Charles U. Pittman (Journal of Environmental Management, 2026)

Sugarcane polyphenols modulate gut microbiota and odor-associated metabolites during in vitro fecal fermentation of elderly - Hongye Li; Yun Bian; Yi Wu; Xueqing Hang; Mengqing Zhang; Luchuan Gao; Yifei Dong; Tanhang Mu; Wei Zhao (Food Bioscience, 2026)

Strength and non-coaxiality behavior of warm frozen silt under inclined principal stress axes - Furong Liu; Wei Ma; Yanhu Mu; Zhi Wen; Mingde Shen; Pengfei He (Engineering Geology, 2026)

Organic carbon burial and ocean redox modulated biotic recovery after the latest Ordovician crisis - Wei Tang; Mu Liu; Heng-Ye Wei; Li-Guang Wu; Kai Lu; Jian Wang; Xian-Hua Li (Earth and Planetary Science Letters, 2026)

Regulation of photosynthesis by exogenous MeJA under phosphorus deficiency: a review - Siyao Zhang; Xinxin Wei; Bin Qiao; Junjie Cui; Rongrong Zhang; Tingting Mu; Guobin Zhang (Plant Cell Reports, 2026)

A Medial Paralemniscal Pth2ergic Circuit Contributing to Aversive and Anxiety-Like Behaviors - Zixu Zhang; Shuyan Geng; Chuanyao Sun; Shengru Hu; Tianxiang Xu; Wei Xie; Mingdao Mu (Neuroscience Bulletin, 2026)

Lithofacies Identification and Classification Based on Least Squares Support Vector Machine Optimized by Sparrow Search Algorithm - Chenyang Mu; Zhongjie Guo; Guangxu Wang; Xiaoxiao Zhang; Cheng Qian; Changsong Lin; Yang Chen; Yougong Wang; Wei Wu (Mathematical Geosciences, 2026)

A lightweight detection algorithm for cereal weed recognition based on deep learning - Xiao-Wei Dong; Lin-Feng Wang; Xi-Mu Zhang; Ming Wang; Wei-Kai Li (Crop Protection, 2026)

Genome-wide association study identifies key SNP and glutamate receptor 4 linked to heat tolerance in Zhikong scallop Chlamys farreri - Zhi Liu; Mingyi Sui; Zujing Yang; Haitao Yu; Qianqian Mu; Lijingjing Bao; Wenhui Jiang; Wei Lu; Qiang Xing; Zhenmin Bao; Xiaoting Huang (Aquaculture, 2026)

Stabilization stage dissolved oxygen and contact-stabilization time ratio synergistically govern quorum sensing-mediated sludge bulking in the high-rate contact-stabilization process - Zhongqi Jiang; Shan Qiu; Mengxuan Deng; Mengqi Fu; Zikun Jin; Mu Yuan; Wei Zhang; Chuandong Wu (Water Research, 2026)

Integrated utilization design of ore and material: Preparation of nickel-based layered double hydroxides by extracting nickel from pentlandite and doping Fe to improve photocatalytic hydrogen production performance - Xiaolong Bi; Wenning Mu; Anlu Wei; Zhigang Hou; Mengjie Han; Xuefei Lei; Shaohua Luo (Process Safety and Environmental Protection, 2026)

Dual mutations containing E198A in β-tubulin eliminate the negative cross-resistance between carbendazim and diethofencarb in Corynespora cassiicola - Jingkun Han; Jiamei Zhu; Jin Li; Dicheng Ma; Wei Mu; Hongqiang Dong; Feng Liu (Pesticide Biochemistry and Physiology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Spatial characterization and health risk evaluation of residual phenol five years after a river pollution incident - Tingting Liu; Fengjing Song; Yiming Sun; Zhen Ding; Hao Zheng; Shixuan Hao; Hong Xu; Yan Liu; Chao Wang; Xiaomin Xie; Mu Zhu; Peixuan Shen; et al. (Journal of Hazardous Materials, 2026)

Aridity controls on the dominance of soil mineral-associated and particulate organic carbon in the Qinghai-Tibet Plateau - Hebin Liu; Mei Mu; Cuicui Mu; Kun Li; Yuguo Wei; Pengsi Lei; Fumei Liu; Xinlong Du; Shijie Li; Jianyu Li (Global and Planetary Change, 2026)

Corrigendum to “An overview of cyclodextrin on the detection and removal of mycotoxin: Recent advances and future prospects” [165 (2024) 110660] - Yan Shi; Wei Xu; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Control, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Efficient generation and utilization of high-valent cobalt-oxo in nanoconfined catalytic membranes for enhanced antibiotic degradation - Wei Zhang; Kaiming Fan; Mu Li; Weihua Xu; Yanling Liu; Shengji Xia (Chemical Engineering Journal, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Structural diversity and properties of bio-based surfactants with their potential applications - Homely Isaya Mtui; Wei Wang; Shi-Zhong Yang; Bo-Zhong Mu (Bioresource Technology, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

A hybrid model driven by remotely-sensed data for simulating the impact of high spatiotemporal variations in fertilization and atmospheric N2O on N2O emissions in paddy fields - Wei Jiang; Xiang Gao; Housheng Wang; Xuerong Lang; Shuai Shen; Xian Hu; Linkai Wen; Qinchun Xu; Yan zhang; Xiaosan Jiang; Jinyang Wang; Yanfeng Ding; et al. (Agricultural and Forest Meteorology, 2026)

Ground validation of dust multi-properties analyzer onboard Tianwen-2 - Xu Tan; Cunhui Li; Jiajie Wang; Zhongcheng Mu; Zecheng Cui; Meng Chen; Xin Ren; Xiaodong Liu; Yan Su; Wei Wang; Renhao Tian; Jiawei Li (Advances in Space Research, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

SikaPointNet++: a method for sika deer point cloud segmentation and body dimensions measurement fusing octree-accelerated sampling and morphological enhancement - Haotian Gong; Yinglun Li; Jinfan Wei; Yu Sun; Tianli Hu; Juanjuan Fan; Zhipeng Li; He Gong; Ye Mu (Computers and Electronics in Agriculture, 2025)

Excavation-induced soil disturbance assessment of soft clay behind the diaphragm wall - Yan-Guo Zhou; Mu-Zhi Li; Yu Tian; Jun-Neng Ye; Wei-An Lin; Yun-Min Chen (Tunnelling and Underground Space Technology, 2025)

Application of activated water irrigation technology: A sustainable way to improve soil fertility and crop adaptability in the sandy area of southern Xinjiang - Xiaoxian Duan; Quanjiu Wang; Weiyi Mu; Changkun Ma; Kai Wei; Yan Sun; Xue Zhao (Soil and Tillage Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Performance of constructed wetland-microbial fuel cell in treating Cd(II)-containing wastewater and bioelectricity generation - Wei Wei; Zhehan Liang; Xiaorui Sun; Caiyun Han; Shiyong Huang; Chunxia Mu (Journal of Water Process Engineering, 2025)

Ore-forming process and fluid development at Nanpo Au deposit, Luang Prabang-Loei Belt (NW Laos): Evidence from H-O-S-Pb isotopes and inclusions - Wei Wang; Hui Li; Jie Gan; Fuhao Xiong; Yu Gan; Bin Wang; Junqing Mu; Huan Liu (Journal of Geochemical Exploration, 2025)

Unraveling humidity's dual effects on trace methane photocatalytic ozonation: Enhanced radical generation versus active site blockade - Junyu Ying; Yun Wang; Haiyuan Zhang; Yang Bai; Jiahua Zhu; Xiaohua Lu; Wei Li; Liwen Mu (Journal of Environmental Chemical Engineering, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Current advances in in-situ bioelectroremediation for trichloroethylene (TCE) -contaminated groundwater: Progress, challenges, and outlook - Hania Hassan; Aslia Asif; Bashir Hussain; Safia Noorani; Arslan Abbas; Shih-Wei Huang; Bing-Mu Hsu (Journal of Environmental Chemical Engineering, 2025)

Construction of smartphone-assisted electrochemical molecularly imprinted sensor based on magnetic MOF@COF as a novel platform for portable and sensitive detection of staphylococcal enterotoxin B - Wei Hu; Minghao Ma; Bin Du; Yikan Zhao; Jiang Wang; Bing Liu; Xihui Mu; Zhangyan Hu; Zhihao Yi; Zhaoyang Tong (Journal of Environmental Chemical Engineering, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

CRISPR/Cas9-mediated knockout of epsA validates its key role in exopolysaccharide production of lactic acid bacteria - Lai Jiang; Yanshu Hu; Wei Gong; Guangqing Mu; Shujuan Jiang (Food Bioscience, 2025)

Self-healing, highly stretchable, recyclable PU-curcumin elastomer with substrate-sensitive solid-state fluorescence - Linjie Wei; Xiubin Xu; Hongchun Mu; Wantong Lin; Jiahui Tang; Jieran Li; Jianwei Liu; Haitao Dong; Danfeng Yu; Xu Wu (Chemical Engineering Journal, 2025)

Asymmetric actuators via lignin-cellulose nanofibrous composite films with programmable wet-light dual-responsiveness - Qiang Mu; Qiangli Zhao; Min Mao; Yao Liu; Jie Tao; Jiahao Kang; Wei Yong; Xinhai He; Jianhua Ma; Jianwei Li (Carbohydrate Polymers, 2025)

Correction to: Unveiling the potential of bio-organic fertilizers to enhance crop yield and improve soil and microbial environments: A meta-analysis in China - Xiaofang Huang; Wei Sun; Chengqun Yu; Peili Shi; Junxi Wu; Fadong Li; Ran Xiao; Jialuo Yu; Jiabao Wang; Tao Mu (Plant and Soil, 2025)

TiO2-Doped Fe-Tailings Heterogeneous Catalysts: Engineering Synergistic Photocatalytic-Fenton Pathways for High-Efficiency Phenol Mineralization - Wen-hao Zhang; Yu Wei; Qi Yu; Chun-heng Wang; Xue-fei Lei; Shao-hua Luo; Huan-huan Chen; Wen-ning Mu (International Journal of Environmental Research, 2025)

Evaluation of mechanical properties and geological features of highly sandy dolomite: consequences for engineering safety - Meiqian Wang; Wei Xu; Hongzhong Xu; Hongyuan Mu; Jian Mi; Yonghong Wu; Yangxing Wang; Baofa Cai (Bulletin of Engineering Geology and the Environment, 2025)
The Central Yunnan Water Diversion Project (CYWD Project) is a crucial water source initiative within Yunnan’s revitalization strategy. However, significant engineering challenges arise, such as tunnel mud and water inrush due to the presence of highly sandy dolomite. Therefore, understanding the mechanical properties of this dolomite is essential for ensuring safe construction in the tunnel engineering of the CYWD Project. This paper examines the highly sandy dolomite found in the Sinian strata of Zbdn and Zbd, located along the Yuxi section of the tunnel line, using both micro and macro testing methods. Microscopic analyses, including slice identification, CT scanning, and scanning electron microscopy, were conducted to determine the primary geological characteristics and classification standards of the sandy dolomite. Additionally, macro tests, such as in-situ needle penetration tests (NPT), uniaxial compressive strength tests (UCS), and shear tests, were performed. Using the least squares method and regression analysis, relationships between the needle penetration index (NPI), UCS, and shear strength were established. This study established reliable relationships between the needle penetration index, uniaxial compressive strength, and shear strength parameters of highly sandy dolomite encountered in the CYWD Project. The geological features were also characterized using macro- and micro-scale testing, providing a theoretical basis for the project’s design and safety. This conversion relationship offers a theoretical basis for the design, construction, and safety evaluation of the CYWD Project. The parameters developed are sufficiently reliable for evaluating engineering in areas with highly sandy dolomite. Graphical abstract

A hybrid model based on machine learning and improved Jayaweera-Mikkelsen model to simulate NH3 volatilization in paddy field water - Xuerong Lang; Xiang Gao; Housheng Wang; Wei Jiang; Shuai Shen; Xian Hu; Linkai Wen; Qinchun Xu; Yan Zhang; Jinyang Wang; Yanfeng Ding; Yue Mu; et al. (Agricultural and Forest Meteorology, 2025)

Facile synthesis of high loading and highly electron-delocalized Co single-atom catalyst for PMS activation: An in-depth study of molecular orbital and catalytic mechanisms - Mu Li; Dongsheng Xia; Wei Zhang; Feiyun Sun; Guan Zhang; Lin Lin; Zhengjun Gong; Bing Li; Xiao-yan Li (Journal of Hazardous Materials, 2025)

Microbial and enzymatic strategies for aflatoxin control: Integrating intelligent detection and computational design - Binbin Ouyang; Wei Xu; Dawei Ni; Wenli Zhang; Junmei Ding; Wanmeng Mu (Food Chemistry, 2025)

Epigenetic transgenerational effects of prenatal exposure to 2,2′,4,4′-tetrabromodiphenyl ether on sperm function and DNA methylation in rat offspring - Ching-Shu Lai; Wei-Cheng Hsu; Jenq-Renn Chen; Bing-Mu Hsu; Kuo-Hsin Lee; Ping-Hsun Wu; Ping-Chi Hsu (Food and Chemical Toxicology, 2025)

Emissions and carbon isotopic signatures of polycyclic aromatic compounds (PAHs, OPAHs) produced by coking in China - Jiajie Li; Ling Mu; Xiaofan Li; Xiaofeng Liu; Huiling Bai; Chuanyang Feng; Xin Jiang; Ying Wei; Chenhui Li (Environmental Pollution, 2025)

Dynamic covalent assembly of hierarchical COF hollow fibers for selective dye remediation - Huiling Chen; Xiubei Yang; Guiping Yang; Yuhe Mu; Chengbing Yu; Wei Zhang; Gaofeng Zeng (Desalination, 2025)

Synergistic Co single-atom/nanoparticle catalysis enables stable hydrogenation of levulinic acid to gamma-valerolactone with formic acid - He Huang; Wei Zhang; Jianrong Zeng; Mengke Liu; Han Lin; Liwen Mu; Xin Feng; Xiaohua Lu; Lilong Zhang; Jiahua Zhu (Chemical Engineering Journal, 2025)

Why not use tertiary amines to prepare anion-exchange membranes for desalination with electrodialysis? - Shuaijun Yu; Yixiang Yu; Yan Zhang; Yangbo Qiu; Tong Mu; Ming Li; Zhipeng Xu; Qiang Wei; Jiangnan Shen (Chemical Engineering Journal, 2025)

Field observations on temperature characteristics and insulation performance of an extra-long highway tunnel in high-altitude cold regions - Lingjie Li; Yanhu Mu; Xiaoming Zhu; Wei Ma; Zhaohui Yang; Kun Zhang; Lijie Zhang (Cold Regions Science and Technology, 2025)

Unveiling the potential of bio-organic fertilizers to enhance crop yield and improve soil and microbial environments: A meta-analysis in China - Xiaofang Huang; Wei Sun; Chengqun Yu; Peili Shi; Junxi Wu; Fadong Li; Ran Xiao; Jialuo Yu; Jiabao Wang; Tao Mu (Plant and Soil, 2025)

Elucidating the suppressive role of native bacterial traits against root-knot nematodes to control plant-parasitic effect in serpentine hostile rhizosphere soil - Aslia Asif; Liang-Yu Lin; Ping-Chi Hsu; Suprokash Koner; Zeng-Yei Hseu; Tsui-Kang Hsu; Shih-Wei Huang; Bing-Mu Hsu (Applied Soil Ecology, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

A low-temperature emergency power source designed from warm pastes based on hydrogel - Chuanchao Sheng; Wei Li; Sixie Yang; Xiaowei Mu; Xinyi Sun; Hang Liu; Haoshen Zhou; Ping He (Science Bulletin, 2025)

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Skeleton engineering of conjugated microporous polymer for highly efficient PM capture in harsh environments - Cailin Guo; Wei Liu; Mengxue Li; Peng Mu; Anli Yi; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Journal of Hazardous Materials, 2025)

Transformation of chloroxylenol in real sewer sediments: Key adsorption sites and CYP450-catalyzed biodegradation - Xinhui Xia; Yujia Du; Huizhi Mu; Dan Li; Shuocheng Shao; Qingliang Zhao; Liangliang Wei (Journal of Hazardous Materials, 2025)

Chromium deposition enhances the tolerance of Chlorella vulgaris to microplastics - Yuanyuan Wei; Xuan Hou; Xiangang Hu; Li Mu (Journal of Hazardous Materials, 2025)

Laccase-mimicking chiral Cu-nanozymes for enantioselective catalysis of phenolic substrates - Qiaodan Du; Zhihao Mu; Dan Liang; Xinman Han; Yuan Zhao; Wei Ma (Journal of Hazardous Materials, 2025)

Ammonium removal characteristics and metabolic mechanisms of the sulfate-tolerant strain Halomonas piezotolerans X0511 - Xiao You; Dongjian He; Man Jiang; Mengting Zhen; Xia Zhu; Hansheng Wei; Xiaopeng Wang; Ce Shi; Changkao Mu; Chunlin Wang; Yueyue Zhou (Journal of Environmental Management, 2025)

Optimizing biogas residue composting: Impact of biochar and zeolite co-loaded with lignocellulose-degrading microbial agents on degradation, humification, and microbial ecology - Hong Chang; Ruian Lin; Xiaohong Su; Xinrui Xu; Wei Liu; Yilin Zhang; Zeyan Mu; Xin Wang; Anina James; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Oyster shell immobilized nano zero-valent iron for enhancing methane production from carbohydrate-rich food waste: Characterization, performance, and mechanism - Xiaofan Ding; Wei Jiang; Fangyuan Feng; Bochang Feng; Yanfei Li; Yongfang Zhang; Chuanshun Zhi; Chunhui Zhao; Jingyang Luo; Hui Mu (Journal of Environmental Chemical Engineering, 2025)

Solidification/stabilization mechanisms of uncalcined waste concrete powder and ground granulated blast slag on lead-contaminated soil: From nanosacle to macroscale - Wei Zhang; Fang-Yuan Mu; Qiang Xue; Jiang-Shan Li (Journal of Environmental Chemical Engineering, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Development of a CD3ε mAb that can identify and in vitro activate T cells in large yellow croaker (Larimichthys crocea) - Zhichao Fang; Yi Cao; Haokai Chen; Jie Cheng; Ming Geng; Jiong Chen; Yinnan Mu; Kang Li; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2025)

Diversification to extinction: oceanic and climatic context of the Ordovician - Mu Liu; Xiujuan Bao; David A.T. Harper; Thomas Algeo; Mingyu Zhao; Matthew Saltzman; Wang Zhang; Daizhao Chen; Shuai Yuan; Yihui Chen; Mengyu Wei; Junpeng Zhang; et al. (Earth-Science Reviews, 2025)

Flexible and wearable strain sensor based on SSt/PAA/G composite hydrogel for human–machine interaction applications - Jinru Liu; Shenghua Lv; Yanlu Mu; Dequan Wei; Ying Chen; Tingxiang He; Jialong She; Leipeng Liu (Chemical Engineering Journal, 2025)

Lymph node-targeted delivery of cancer vaccine with natural plant derivatives potentiates antitumor efficacy through improved antigen presentation - Jiankang Mu; Zhonglian Wei; Ziyi Chen; Ping Wang; Haoran Wang; Peng Cao (Chemical Engineering Journal, 2025)

Phase-interfacial engineering of 2H@1 T-WS2-x cocatalyst to accelerate H2 production on SnS2 - Jianchun Wang; Nan Mu; Ruixin Xu; Xin Hong; Yanyu Liu; Wei Zhou (Chemical Engineering Journal, 2025)

Corrigendum to “Study the photocatalytic mechanism of the novel Ag/p-Ag2O/n-BiVO4 plasmonic photocatalyst for the simultaneous removal of BPA and chromium(VI)” [Chem. Eng. J. 361 (2019) 1352–1362] - Wei Zhao; Jin Zhang; Fengxia Zhu; Feihu Mu; Lili Zhang; Benlin Dai; Jiming Xu; Anfeng Zhu; Cheng Sun; Dennis Y.C. Leung (Chemical Engineering Journal, 2025)

Ti3C2Tx/TiO2/CuO nanocomposite-based gas sensors for high-performance ethanol detection at room temperature - Ming Zhou; Xuefeng Hu; Zhiyuan Liu; Weiwei Qin; Liping Tan; Jilei Yang; Debao Yu; Qingqing Mu; Anquan Bao; Yali Bi; Wenjuan Yu; Wei Zhang (Chemical Engineering Journal, 2025)

Tailoring key intermediates and interfacial water at Ag92Ru8 aerogel toward sustainable ammonia synthesis from nitrate - Junjie Chen; Xiaomei Xing; Sisi Wen; Mengyuan Li; Di Liu; Wenji Jiang; Xinyi Shao; Ruikai Qi; Yumei Yang; Ming Mu; Zheng-jie Chen; Bing Zhao; et al. (Chemical Engineering Journal, 2025)

Interface modification of fluopyram-loaded microcapsules using Fe3+/lignosulfonate via coordination and electrostatic interactions to improve nematicide rhizosphere utilization - Haichao Cao; Yanhou Zhao; Jiangzhou Li; Kuai Dai; Lijun Jiang; Wenzheng Ling; Wei Mu; Chao Feng; Dan Chen; Jinguang Yang (Chemical Engineering Journal, 2025)

Ubiquitination: A non-negligible modulator in doxorubicin-induced cardiotoxicity - Can Gao; Changxu Lu; Jinwen Wei; Zhongyi Mu; Mingli Sun; Dan Dong; Zhenning Liu (Chemico-Biological Interactions, 2025)

What does the dairy farming bring to the desertified soil? A case study - Zixi Han; Jianfei Zeng; Xu Zhao; Yanyan Dong; Yongsong Mu; Sha Wei; Yong Hou; Ziyu Han (Agricultural Systems, 2025)

Tissue-Selective Separation Mechanism of Multi-type Soft Tissues Under Waterjet Impact for Low-Trauma Cutting Surgery - Jiaqi Zhao; Xiao-Fei Song; Xiaoxian Wei; Jiuke Mu; Peng Peng; Wenli Yu (Annals of Biomedical Engineering, 2025)

Two novel 5,5-spiroketal sesquiterpenoid isomers from the roots of Angelica biserrata (R. H. Shan &Yuan) C. Q. Yuan & R. H. Shan - Fuyong Ni; Rongrong Li; Zixian Xie; Ying Li; Ningning Xu; Xuanyu Mu; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Xue Xie; Wei Xiao (Natural Product Research, 2025)

Recent advances on health effects and biological production of functional monosaccharide d-mannose - Yehong Cao; Yihan Chen; Wei Xu; Yingying Zhu; Wenli Zhang; Dawei Ni; Wanmeng Mu (Trends in Food Science & Technology, 2025)

Epithelial cells facilitate tissue fibrosis through early growth response-1 overexpression in IgG4-related disease - Ruijie Sun; Qinhuan Luo; Mu Wang; Linyi Peng; Wei Wei; Yanmei Li; Jiaxin Zhou; Yuxue Nie; Jingna Li; Qing Zhong; Yunyun Fei; Mengtao Li; et al. (Science Bulletin, 2025)

Wind-tide modulated net ecosystem metabolism in a Changjiang River Estuary aquaculture zone during mid-autumn - Di Wu; Kui Wang; Guoquan Wang; Qinglin Mu; Wei Fan; Dawei Xu (Marine Environmental Research, 2025)

A runoff prediction approach based on machine learning, ensemble forecasting and error correction: A case study of source area of Yellow River - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Baiyinbaoligao; Jiahua Wei; Jie Gao; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2025)

STING inhibition suppresses butachlor-induced splenic macrophage pyroptosis and M1 polarization via cGAS-STING signaling - Ru-Yang Zhao; Mu-Zi Li; Qi-Qian Wang; Fu-Wei Jiang; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Effects of metal oxides loaded with biochar on adsorption of cationic and anionic metals: A meta-analysis - Yang Yu; Xinwei Chen; Lingxin Zhao; Shufei He; Likui Feng; Weixin Zhao; Huizhi Mu; Qingliang Zhao; Liangliang Wei (Journal of Environmental Management, 2025)

Identification of a novel DON dehydrogenase and computational insights into the decisive role of cofactor affinity in DON detoxification - Binbin Ouyang; Zhaolin Huang; Chengfei Wang; Yurong Sun; Junmei Ding; Wei Xu; Wanmeng Mu (Food Bioscience, 2025)

Multi-omics investigation into microbial community succession and flavor compound dynamics during post-fermentation of Doubanjiang - Ling Chen; Wei Su; Yingchun Mu; Zhuo Chen; Yu Jiao; Linzhu L; Huayan Luo; Zhongle Lu (Food Bioscience, 2025)

Unraveling the main chemical mechanism of PM2.5 pollution caused by open burning of sugarcane straw during winter in southern China: The Pivotal Role of NOx and NH3 Oxidation-Neutralization - Xu Wei; Guiyun Liang; Jingying Mao; Junchao Yang; Yijun Mu; Chuan Nong; Dabiao Zhang; Jiahui Lu; Xishou Huang; Ying Wu; Zhaoyu Mo (Environmental Pollution, 2025)

Hofmeister effect guided dual-crosslinked sodium alginate-based hydrogel with super-stretchable, self-adhesive, and antibacterial properties for flexible sensors in human activity monitoring - Tingxiang He; Shenghua Lv; Ying Chen; Yanlu Mu; Jinru Liu; Jialong She; Dequan Wei; Leipeng Liu (Chemical Engineering Journal, 2025)

Synergistic microstructure regulation of coal tar pitch based‑carbon by pre-oxidation and iodine treatment for its high-plateau-capacity sodium storage - Yuli Wei; Qing Wang; Qing Liu; Rongzhe Wang; Shaohua Luo; Lixiong Qian; Yahui Zhang; Pengqing Hou; Shengxue Yan; Xin Liu; Jing Guo; Wenning Mu (Chemical Engineering Journal, 2025)

Unlocking the enhanced trichloroethylene bioremediation potential of mud volcano by targeting synergistic microbial stimulation and electron transfer using microbial fuel cells (MFCs) - Bashir Hussain; Bing-Mu Hsu; Aslia Asif; Danish Ali; Ashiq Hussain; Shih-Wei Huang (Chemical Engineering Journal, 2025)

Enhancing methanogenesis from long-chain fatty acids (LCFA) and enrichment of novel bacteria with resuscitation-promoting factors - Bo Fang; Yi-Fan Liu; Hao-Xun Wei; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2025)

Exogenous brassinolide alleviates the autotoxicity induced by vanillin in Lagenaria siceraria - Yiyue Jiang; Xiaodi Zhang; Hongmei Mu; Shan Liu; Saike Qi; Jinlei Wang; Shengxin Wei; Yixue Wang (Plant and Soil, 2025)

Transcriptome Analysis Revealed the Immune and Metabolic Responses of Grass Carp (Ctenopharyngodon idellus) Under Acute Salinity Stress - Leshan Ruan; Baocan Wei; Yanlin Liu; Rongfei Mu; Huang Li; Shina Wei (Fishes, 2025)
Freshwater salinization, an escalating global environmental stressor, poses a significant threat to freshwater biodiversity, including fish communities. This study investigates the grass carp (Ctenopharyngodon idellus), a species with the highest aquaculture output in China, to elucidate the molecular underpinnings of its physiological adaptations to fluctuating salinity gradients. We used high-throughput mRNA sequencing and differential gene expression profiling to analyze transcriptional dynamics in intestinal and kidney tissues of grass carp exposed to heterogeneous salinity stressors. Concurrent serum biochemical analyses showed salinity stress significantly increased Na+, Cl−, and osmolarity, while decreasing lactate and glucose. Salinity stress exerted a profound impact on the global transcriptomic landscape of grass carp. A substantial number of co-regulated differentially expressed genes (DEGs) in kidney and intestinal tissues were enriched in immune and metabolic pathways. Specifically, genes associated with antigen processing and presentation (e.g., cd4-1, calr3b) and apoptosis (e.g., caspase17, pik3ca) exhibited upregulated expression, whereas genes involved in gluconeogenesis/glycolysis (e.g., hk2, pck2) were downregulated. KEGG pathway enrichment analyses revealed that metabolic and cellular structural pathways were predominantly enriched in intestinal tissues, while kidney tissues showed preferential enrichment of immune and apoptotic pathways. Rigorous validation of RNA-seq data via qPCR confirmed the robustness and cross-platform consistency of the findings. This study investigated the core transcriptional and physiological mechanisms regulating grass carp’s response to salinity stress, providing a theoretical foundation for research into grass carp’s resistance to salinity stress and the development of salt-tolerant varieties.

Mud volcanoes and microbial communities: Unraveling the mysteries of formation, features, and occurrence - Senthil Kumar Rajendran; Suprokash Koner; Bashir Hussain; Hsin-Chi Tsai; Zeng-Yei Hseu; Jung-Sheng Chen; Shih-Wei Huang; Danish Ali; Muhammad Adil Khan; Bing-Mu Hsu (Journal of Asian Earth Sciences, 2025)

Bone marrow microenvironment-targeted yolk-shell nanoparticle enhances acute myeloid leukemia chemotherapy by preventing endothelial cell/ECM-mediated adhesion - Shiyi Hong; Pei Peng; Yutian Huang; Siying Cai; Cao Yao; Tongtong Huang; Yulu Ying; Wei Li; Yang Xiong; Mancang Gu; Guilin Cheng; Chaofeng Mu (Chemical Engineering Journal, 2025)

Coordinated diffusional and biochemical limitations underlie age-related decline in photosynthetic capacity of rice leaves - Haifeng Xiong; Fengshuo Ma; Mengdi Mu; Jingwen Wang; Yunmin Wei (Photosynthesis Research, 2025)

Biogeography and Niche Evolution of Odorrana schmackeri Complex in Southern China - Shize Li; Bin Wang; Jing Liu; Haijun Su; Gang Wei; Lang Mu; Tuo Shen; Zhitong Lyu; Yingyong Wang; Houqiang Xu (Journal of Biogeography, 2025)
Aim The Odorrana schmackeri complex (OSC), widely distributed across southern China, presents intriguing mysteries regarding its diversification dynamics. Resolving these evolutionary enigmas would establish a crucial foundation for understanding biogeographic evolution in this topographically complex region. Therefore, we integrated phylogenetic, demographic, and ecological niche analyses to elucidate the roles of ancient tectonism, Quaternary climatic fluctuations, and niche evolution in shaping its diversification and distribution. Location Southern China. Methods Using two mitochondrial and eight nuclear genes, we reconstructed phylogenetic relationships, estimated divergence times and assessed population dynamics. Ecological niche models (ENMs) were optimised via the ‘Kuenm’ package, and niche overlap, equivalency, and similarity were quantified using the ‘ecospat’ R package. Acestral niche and climatic tolerances reconstruction were used in the ‘phyloclim’ package. Results The OSC comprises nine species and originated from a mid‐Miocene ancestor (~12.55 Ma). Mitochondrial phylogeny resolved four deeply divergent clades, while nuclear gene phylogeny revealed incomplete lineage sorting (ILS) and historical gene flow (STRUCTURE, K = 7; JML, p > 0.05). Post‐last glacial maximum (LGM) expansions (~0.02 Ma) facilitated secondary contact in sympatric zones, where niche conservatism dominated between sister species. Ancestral niche reconstruction identified precipitation variables as key drivers of early divergence, while thermal tolerances evolved conservatively. The results indicated that Miocene uplift of the Qinghai‐Tibet Plateau (~12.55–8.70 Ma) promoted southward expansion, while Pliocene‐Pleistocene (~5.58–2.40 Ma) river reorganisations fragmented and later connected populations. Main Conclusions The OSC's diversification reflects the interplay between Miocene–Pliocene tectonism and Quaternary climatic cycles. While ancestral niche divergence along precipitation gradients initiated speciation, post‐LGM sympatry favoured conservatism in thermal microhabitats. Combining multilocus phylogenetics, demographic inference, and niche modelling resolves the rapid‐radiating models in the frog complex and highlights the dynamic roles of landscape features in shaping biogeographic patterns of them.

Formyl-phloroglucinol meroterpenoids with Nrf2 inhibitory activity from Eucalyptus globulus leaves - Wei Liu; Yaodong Xia; Lejie Zhang; Xin Chen; Zhuo Zhang; Yu Mu; Jialin Xu; Xueshi Huang; Liya Li (Phytochemistry, 2025)

Understanding phytotoxicity of fosthiazate on crop seedlings through uptake kinetics, ROS burst and chloroplast metabolism - Jiamei Zhu; Min Jiang; Wen Sun; Xiaochi Liu; Wenjian Dou; Yujie Gao; Tao Zhang; Jianfeng Tang; Wei Mu; Nan Zou; Feng Liu (Journal of Hazardous Materials, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

Nucleotide loss caused by alkaline phosphatase renaturation during infant formula production - Xiangxin Wang; Zhewen Wei; Sinan Mu; Xueyin Qu; Jianqiao Li; Hong You; Yang Xie; Shilong Jiang; Jianguo Sun; Bailiang Li; Qinggang Xie (Food Chemistry, 2025)

Corrigendum to “Changes of unique flavor substances and metabolic pathway brought by Lacticaseibacillus rhamnosus WH. FH-19 fermented milk during fermentation and storage stage: HS-SPME-GC-MS and HPLC-MS-based analysis” [Food Bioscience 65 (2025) 1–11/105974] - Lu Feng; Jingxia Yang; Liping Sun; Xiaoyan Zhu; Wei Lan; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

Molecular and functional identification of a LC3C homolog in large yellow croaker (Larimichthys crocea) - Zuyun Wei; Yinnan Mu; Chunxiang Ai; Xinhua Chen (Fish & Shellfish Immunology, 2025)

In vivo imaging tool: High-brightness NIR-II “J-aggregates” based on TICT suppression strategy - Taihe Han; Shuai Mu; Qin Huang; Jiaxing Sun; Xin Lv; Yanxia Zhang; Xiaoyan Liu; Wei Guo; Haixia Zhang (Chemical Engineering Journal, 2025)

The impact of the circular economy pilot policy on green total factor productivity: evidence from a quasi-natural experiment in China - Liang Xie; Xian-zhong Mu; Ming-wei Li; Guang-wen Hu (Clean Technologies and Environmental Policy, 2025)

Could chloroxylenol be used as WBE biomarker in gravity sewers? Fates, behaviors and feasible conditions - Xinhui Xia; Huizhi Mu; Yujia Du; Shuocheng Shao; Yaqun Li; Dan Li; Qingliang Zhao; Liangliang Wei (Water Research, 2025)

Mixing mechanisms of hydrogen-blended natural gas in subsea pipelines: Effects of injection angles - Fenghui Han; Xichen Mu; Ying Wei; Wenhua Li; Zhe Wang (Ocean Engineering, 2025)

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Metatranscriptomics reveals the effect of fermentation by Pediococcus acidilactici and Rhizopus oryzae on the quality of mutton sausages and the mechanism of odor metabolism - Nuo Chen; Weiyi Fu; Li Jiang; Nian Zhang; Yingchun Mu; Wei Su (Food Chemistry, 2025)

Microbial absolute quantification and metabolomics reveal the impact of partial KCl substitution for NaCl on the flavor quality of Zao Chili - Kangli Yang; Wei Su; Yingchun Mu; Xiaomin Liu; Yuxia Liu; Yongxin Lu (Food Bioscience, 2025)

Predicting and regulating potential zone for heavy metal re-contaminated farmland: Case study in Taiwan - Jieh-Haur Chen; Mu-Chun Su; Meng-Fen Yeh; Wei-Jen Lin; Tzuyang Yu; Ming-Chung Yeh (Environmental Development, 2025)

Construction of the dynamic measurement algorithm for well inclination and azimuth in strapdown stable platform - Feng Sun; Rui Zhang; Yi-feng Wang; Wei Chen; Hui-dong Mu; Rui-wen Feng (Applied Geophysics, 2025)

The Spatial–Temporal Characteristics of Wave Energy Resource Availability in the China Seas - Rui-Zhe Shen; Cheng-Tao Yi; Yu-Nuo Liu; Lei Wang; Kai Wu; Mu-Yu Chen; Chong-Wei Zheng (Journal of Marine Science and Engineering, 2025)
For coastal nations and regions, wave energy provides a localized energy solution, decreasing dependency on external energy sources and fostering the sustainable development of local economies. Effective wave height occurrence (EWHO) represents the availability of wave energy and is a crucial parameter for site selection for optimal wave energy. This paper systematically analyzes the distribution of EWHO in China seas areas using significant wave height (SWH) data in the fifth generation of ECMWF atmospheric reanalysis (ERA5) and key climate indices. Employing methods such as climate statistical analysis, linear regression, significance testing, and trend analysis, the study highlights the temporal and spatial distribution characteristics, variation trends, and correlations with climate indices of EWHO. This research aims to provide technical assistance and decision support for the development of wave energy at sea. The results indicate the following conclusions: (1) The high EWHO in the China seas is predominantly located in northern Nanhai, southern Donghai, and the eastern waters of the Philippine Islands. The EWHO is highest in winter. (2) The growth trend of EWHO is most notable in the sea area east of the line connecting the Ryukyu Islands, Taiwan, and the northeastern Philippines, peaking in spring and being relatively weak in winter. (3) The correlation between NINO3 and EWHO is most significant in Nanhai and the northeastern waters of the Philippines, peaking in February with correlation coefficients ranging from −0.30 to −0.50.

Role of myostatin promoter mutations in growth and molting regulation of Macrobrachium rosenbergii - Qiyao Su; Jie Wei; Yakun Wang; Bai Liufu; Huarong Li; Zhuang Mai; Kunhao Hong; Qiaoyan Zhou; Tianhui Jiao; Xidong Mu; Lingyun Yu (Frontiers in Marine Science, 2025)
Myostatin ( Mstn ), a negative regulatory factor in myocytes, has garnered significant attention. This study focused on the Mstn gene and its 24-base-pair mutant in the promoter region of the giant freshwater prawn ( Macrobrachium rosenbergii ), aiming to investigate the regulatory roles of Mstn and its mutant in M. rosenbergii . The research provides theoretical insights into the functional mechanisms of Mstn in crustaceans. Spatiotemporal expression patterns revealed Mstn presence throughout embryonic development and in various body tissues, with peak expression during the gastrula stage and in the hepatopancreas. During the molting cycle, Mstn expression levels decreased in the order of post-molt (A phase), pre-molt (D3 phase), and molting (E phase). Knockdown experiments targeting two genotypes within the Mstn promoter region significantly reduced growth rates and extended molting cycles compared to control group. Further trials on the F2 generation confirmed these findings, highlighting that promoter knockdown influenced the expression of three molting-related genes and slowed the growth rate of M. rosenbergii . This study clarifies the functional role of Mstn in crustacean growth and molting, providing a foundation for understanding its regulatory mechanisms and offering potential applications in aquaculture.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The effect of Hydrogen-rich water on retinal degeneration in the outer nuclear layer of simulated weightlessness rats - Yuxue Mu; Weihang Li; Dongyu Wei; Xinyi Zhang; Lilingxuan Yao; Xiaofeng Xu; Xiaocheng Wang; Zuoming Zhang; Tao Chen (Life Sciences in Space Research, 2025)

PFASs contamination in the LongTing Lake sediments: Vertical-temporal variation, sources, microbial impacts, and risk assessment - Jingshen Zhang; Yang Liu; Yanghui Gong; Naying Wei; Zeyu Liu; Xiaohui Hou; Yue Mu; Xiaoli Zhao; Shengyong Jia; Fengchang Wu (Journal of Water Process Engineering, 2025)

Sedimentary heavy metal interactions with phytoplankton and zooplankton across the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Environmental Management, 2025)

Rational application of QoIs fungicides to achieve a rice-fungi-fish interaction balance within paddy ecosystems - Hong Li; Xueqing Wang; Beixing Li; Jin Lin; Feng Liu; Wei Mu (Environmental Pollution, 2025)

Polymer-derived C-Sn/SnO2@rGO heterostructures with dual assistance of gallic acid for high-performance lithium-ion batteries - Guanwen Wang; Baoyi Mu; Ke Cao; Chunlei Chi; Chuanqing Wang; Chao Huangfu; Fan Feng; Bin Qi; Qiushi Miao; Xinhou Yang; Zheng Liu; Tong Wei; et al. (Chemical Engineering Journal, 2025)

Downregulation of HSPB1 and MGST1 Promotes Ferroptosis and Impacts Immune Infiltration in Diabetic Cardiomyopathy - Yaoli Xie; Bin Liang; Zhijun Meng; Rui Guo; Caihong Liu; Yi Yuan; Wei Mu; Yajing Wang; Jimin Cao (Cardiovascular Toxicology, 2025)

Polydopamine-modified coal fly ash composite electrodes for improved electroadsorption of uranium - Jianfeng Zhang; Yifei Jiang; Mu You; Jing Zhao; Shuwen Xue; Hongxia Fang; Yijun Wei; Zhimei Sun; Tao Zeng; Ziqi Wan; Mai Xu; Yunhu Hu (Journal of Water Process Engineering, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Photo-stimulating dual-network microminiature hydrogels reinforced with silver sulfide nanoparticles for regulated cancer photothermal therapy - Rongqiu Mu; Guanghui Gu; Youyin Xu; Yongming Xi; Gang Wei (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

The use of isomerases and epimerases for the production of the functional sugars mannose, allulose and tagatose from Fructose - Junya Yang; Yingying Zhu; Xu Wei; Dawei Ni; Wenli Zhang; Wanmeng Mu (World Journal of Microbiology and Biotechnology, 2025)

Targeted mutagenesis and functional marker development of two Bna.TAC1s conferring novel rapeseed germplasm with compact architecture - Bin Feng; Yu Wang; Xiaolong Zhang; Tingting Mu; Biaoming Zhang; Yan Li; Haitao Zhang; Wei Hua; Wenya Yuan; Haitao Li (Theoretical and Applied Genetics, 2025)

Single-chain variable fragment-based immunoassay for bioactive natural products - Xiping Cui; Jian Lu; Jinchao Wei; Suqing Zhao; Yiyong Yan; Guo Yin; Bing Wang; Yunping Mu; Peng Li (Phytochemistry Reviews, 2025)

3D Heterogeneous Geological Model of Natural Gas Hydrates in Shenhu Area, South China Sea - Langfeng Mu; Dawang Liu; Yi Zhang; Hailong Lu; Shipeng Wei (Journal of Marine Science and Engineering, 2025)
Natural gas hydrates, as a novel clean energy resource, have attracted widespread attention because of their highly complex reservoir properties, fluid distribution, and phase transitions. In particular, the fluid–solid interactions among hydrates, natural gas, water, and other multiphase components, along with phase state transitions influenced by temperature and pressure and the dynamic reservoir responses induced by hydrate decomposition and synthesis, make their study unique. Consequently, accurately predicting the structure and reservoir properties of natural gas hydrates remains a scientific challenge. In this study, high-resolution 3D seismic data, well logging, and core samples from the Shenhu test area in the South China Sea were utilized for stratigraphic correlation and classification. The hydrate, three-phase mixed, and free gas layers were identified as distinct geological bodies, and detailed stratigraphic subdivisions were performed based on hydrate distribution and physical properties. By integrating stochastic and deterministic modeling approaches, a comprehensive hydrate reservoir model, along with temperature and pressure field models, was established. For the first time, a three-dimensional heterogeneous geological model of the hydrate reservoir was developed for the test exploitation area. This model provides a robust geological foundation for hydrate reservoir studies, numerical simulations, and the formulation of efficient exploitation strategies, contributing to the advancement of natural gas hydrate exploration and production.

Novel neonicotinoid insecticide cycloxaprid exhibits sublethal toxicity to honeybee (Apis mellifera L.) workers by disturbing olfactory sensitivity and energy metabolism - Wei Zhang; Zhiyang Jiang; Mu Ding; Xue Wang; Aidi Huang; Lihong Qiu; Suzhen Qi (Journal of Hazardous Materials, 2025)

Changes of unique flavor substances and metabolic pathway brought by Lacticaseibacillus rhamnosus WH. FH-19 fermented milk during fermentation and storage stage: HS-SPME-GC-MS and HPLC-MS-based analysis - Lu Feng; Jingxia Yang; Liping Sun; Xiaoyan Zhu; Wei Lan; Guangqing Mu; Xuemei Zhu (Food Bioscience, 2025)

Extraction of copper from chalcopyrite by clean and efficient chlorination process to prepare Cu-Fe bimetallic oxide for Li-ion batteries: A facile method in view of sustainable engineering - Xiaolong Bi; Wenning Mu; Anlu Wei; Mengjie Han; Xuefei Lei; Qing Wang; Shaohua Luo (Chemical Engineering Journal, 2025)

Enhanced electrochemical performance of NCM811-based batteries by using a multifunctional electrolyte additive - Aijia Wei; Shuxing Mei; Jinping Mu; Peng Liu; Xue Bai; Rui He; Xiaohui Li; Yuxin Niu; Lihui Zhang; Zhenfa Liu; Lei Wang (Chemical Engineering Journal, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Regulatory Roles and Therapeutic Potential of miR-122-5p in Hypoxic-Ischemic Brain Injury: Comprehensive Review - Abdulaziz S. Bamahel; Xun Sun; Wei Wu; Chenxi Mu; Jia Liu; Sheng Bi; Hui Xu (Cell Biochemistry and Biophysics, 2025)

Integrated Navigation Algorithm for Autonomous Underwater Vehicle Based on Linear Kalman Filter, Thrust Model, and Propeller Tachometer - Haosu Zhang; Yueying Cai; Jin Yue; Wei Mu; Shiyin Zhou; Defei Jin; Lingji Xu (Journal of Marine Science and Engineering, 2025)
For the purpose of reducing the cost, size, and weight of the integrated navigation system of an AUV (autonomous underwater vehicle), and improving the stealth of this system, an integrated navigation algorithm based on a propeller tachometer is proposed. The algorithm consists of five steps: ① establishing the resistance model of AUV, ② establishing the thrust model, ③ utilizing the measured speeds obtained from the AUV’s voyage trials for calibration, ④ discrimination and replacement of outliers from the tachometer measurements, and ⑤ establishing a linear Kalman filter (LKF) with water currents as state variables. This paper provides the modeling procedure, formula derivations, model parameters, and algorithm process, etc. Through research and analysis, the proposed algorithm’s accuracy has been improved. The specific values of the localization error are detailed in the main text. Therefore, the proposed algorithm has high accuracy, a strong anti-interference capability, and good robustness. Moreover, it exhibits certain adaptability to complex environments and value for practical engineering.

Combination mechanism and dimethyl ether removal performance of organic-bound water in kitchen waste - Jipeng Sun; Wei Zhu; Jun Zhong; Biao Mu; Xin Wang; Xinyi Wang; Yucheng Xu; Jun Cao; Naixi Lin (Waste Management, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

Heatwaves increase the polystyrene nanoplastic-induced toxicity to marine diatoms through interfacial interaction regulation - Xuan Hou; Xiangang Hu; Li Mu; Yuanyuan Wei (Journal of Hazardous Materials, 2025)

Recent developments in photo-fermentative hydrogen evolution: Fundamental biochemistry and influencing factors a review - Yaksha Verma; Jibran Iqbal; Mu. Naushad; Aishwarya Bhaskaralingam; Amit Kumar; Pooja Dhiman; Chin Wei Lai; Gaurav Sharma (Journal of Environmental Management, 2025)

Accurate spaceborne waveform simulation in heterogeneous forests using small-footprint airborne LiDAR point clouds - Yi Li; Guangjian Yan; Weihua Li; Donghui Xie; Hailan Jiang; Linyuan Li; Jianbo Qi; Ronghai Hu; Xihan Mu; Xiao Chen; Shanshan Wei; Hao Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Integrated metabolome and transcriptome analysis provides insights into the mechanisms of terpenoid biosynthesis in tea plants (Camellia sinensis) - Junchi Wei; Xingyu Mu; Shaoying Wang; Qi Wei; Luqin Zhu; Xiangna Zhang; Jing Zhang; Xiaobo Liu; Beibei Wen; Meifeng Li; Jianjun Liu (Food Research International, 2025)

Thiol-linked hyaluronic acid-mediated encapsulation of RCR-stabilized gold nanoclusters for hyaluronidase sensing and cellular imaging - Manivannan Madhu; Meng-Yuan Tsai; Ming-Mu Hsieh; En-Yu Lin; Wei-Bin Tseng; Chi-Yu Lu; Wei-Lung Tseng (Carbohydrate Polymers, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Asymmetric synthesis of spiro[4H-chromene-3,3′-oxindoles] via a squaramide-organocatalytic three-component cascade Knoevenagel/Michael/cyclization sequence - Liming Wang; Hongwen Mu; Yuhong Sun; Ying Jin; Wei Zhang (Molecular Diversity, 2025)

Coverage path planning for multi-AUV considering ocean currents and sonar performance - Xukai Mu; Wei Gao (Frontiers in Marine Science, 2025)
Coverage path planning (CPP) for target search by autonomous unmanned vehicle (AUV) involves two crucial aspects: (1) the sonar performance of the AUV is sensitive to ocean environment, such as changes in terrain; and (2) the ocean currents significantly influence AUV dynamics AUV dynamics. To address the CPP of multiple AUVs (multi-AUV) considering both sonar performance and ocean currents, we propose a new integrated algorithm based on the improved Dijkstra algorithm, Particle Swarm Optimization (PSO), and the ELKAI Solve. First, the necessary sampling points for the area coverage are identified based on the sonar detection range at different locations, which is calculated by combining the ocean acoustics model with the sonar equation. Second, an improved Dijkstra algorithm is presented to solve the adjacency matrix of the graph formed by all sampling points under the influence of ocean currents. Third, the PSO algorithm is utilized for task allocation, and the ELKAI solver determines the optimal path for each AUV. Finally, multi-AUV path planning is achieved through iterations of the PSO algorithm and the ELKAI solver. Simulation results demonstrate the outstanding performance and robustness of our integrated algorithm.

AMPK activation by dietary acadesine improves fillet texture in large yellow croaker (Larimichthys crocea) fed a linseed oil-based diet - Shengdi Chen; Zihan Sun; Ningning Liu; Chenbin Yang; Na Li; Lu Li; Chaoqing Wei; Binlun Yan; Huan Gao; Peng Tan; Hua Mu (Aquaculture, 2025)

Structure-selectivity relationship of anion exchange resins with different quaternary amine functional groups for highly selective removal of PFAS from chromium-plating wastewater - Xiangzhe Jiang; Yihua Luo; Shuang Mu; Bojiang Meng; Wei Wang; Gang Yu; Shubo Deng (Water Research, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Mercury isotope evidence for Middle Ordovician photic-zone euxinia: Implications for termination of the Great Ordovician biodiversification event - Mu Liu; Wei Yuan; Chaogang Fang; Xun Wang; Ning Tan; Mingyu Zhao; Xiangli Wang; Thomas J. Algeo; Peng Sun; Xinbin Feng; Daizhao Chen (Gondwana Research, 2025)

Moving in the landscape: Omnidirectional connectivity dynamics in China from 1985 to 2020 - Haowei Mu; Shanchuan Guo; Xingang Zhang; Bo Yuan; Zilong Xia; Pengfei Tang; Wei Zhang; Peng Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2025)

High-performance biomass moisture-electric generators derived from Distillers’ spent grains: Synthesis, photothermal enhancement, and environmental sensing applications - Haichuan Gao; Zihao Feng; Wenjun Li; Jiatian Zhu; Shengdong Mu; Hongkai Zhang; Genqiao Liu; Wei Zhao; Bailiang Xue; Yonghao Ni (Chemical Engineering Journal, 2025)

Durable and degradable adhesive-free wood straw via cell wall activation and self-bonding - Liangxian Liu; Guoqing Mu; Haiyu Li; Haozhou Huang; Yuyan Jiang; Yutong Chen; Ming Wei; Dexiu Min; Jian Li; Yanjun Xie; Zhenqian Pang; Shaoliang Xiao (Chemical Engineering Journal, 2025)

Characterization of deoxynivalenol dehydrogenase from Pelagibacterium sp. SCN 63–126 and its application - Wei Xu; Jiayi Yao; Jingbo Ma; Chen Lu; Chenfei Wang; Yurong Sun; Cuie Guang; Wanmeng Mu (Archives of Microbiology, 2025)

A comprehensive review on the properties, production, and applications of functional glucobioses - Shuqi Zhang; Dawei Ni; Yingying Zhu; Wei Xu; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Cooperative control of leader–follower ships with prescribed performance - Xinjiang Wei; Chengmei Mu; Huifeng Zhang; Xin Hu (Ocean Engineering, 2024)

Role and mechanism of the outer membrane porin LamB in T-2 mycotoxin-mediated extensive drug resistance in Escherichia coli - Fengru Deng; Li Zhao; Ping Wei; Enhua Mai; Meichan Chen; Huixin Yang; Peiqiang Mu; Jun Wu; Jikai Wen; Yiqun Deng (Journal of Hazardous Materials, 2024)

Highly dispersed CuOx decorated ZnO photocatalyst for low-concentration methane removal - Yun Wang; Sheng Xu; Haiyuan Zhang; Yuyin Wang; Enmao Wang; Zeyu He; Jiahua Zhu; Xiaohua Lu; Lilong Zhang; Yang Bai; Kunfeng Zhao; Qingwei Gao; et al. (Journal of Environmental Chemical Engineering, 2024)

Activation of microbial community and enhancement of quality by inoculating Zygosaccharomyces rouxii during the post-fermentation stage of Doubanjiang - Danyu Yan; Qi Qi; Linpei Liu; Lei Feng; Peiyi Deng; Zhuo Chen; Yingchun Mu; Wei Su (Food Research International, 2024)

Opportunities and challenges in developing promising mycotoxin-degrading enzymes with high thermostability and strong pH activity/stability - Binbin Ouyang; Wenli Zhang; Cuie Guang; Wei Xu; Wanmeng Mu (Food Bioscience, 2024)

Directly mining and identifying a cellobiose 2-epimerase with isomerization activity by phylogenetic analysis - Zhaolin Huang; Binbin Ouyang; Jiajun Chen; Guocong Luo; Dawei Ni; Wei Xu; Wanmeng Mu (Food Bioscience, 2024)

A sprayable and rapidly cross-linked hydrogel membrane for fruit preservation - Luxing Wei; Xiaoyong Qiu; Yingwen Mu; Limin Zhang; Jian Shen; Shunji Yang; Xiangyu Zhou; Yungang Gai; Shuyuan Wang; Jun Huang (Food Packaging and Shelf Life, 2024)

Efficient phosphate recovery and treatment of high-phosphorus wastewater using sodium alginate-immobilized microspheres based on aluminum-rich water treatment plant sludge - Guorui Li; Wei Zhu; Jun Zhong; Jipeng Sun; Yichao Wang; Biao Mu; Xin Wang; Yucheng Xu (Environmental Pollution, 2024)

Dynamic characteristics of soil pore structure and water-heat variations during freeze-thaw process - Yajun Shi; Lianhai Zhang; Yanhu Mu; Wei Ma; Xiangbing Kong; Chengsong Yang (Engineering Geology, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Enhancement and Preservation of Tufa Geosites in the Baishuitai Region, Yunnan Province, Southwest China - Hong-Xu Mu; Qing-Wei Song; Gui-Hua Wu; Long-Xin Xu (Geoheritage, 2024)

Identification of a thermostable L-asparaginase from Pyrococcus yayanosii CH1 and its application in the reduction of acrylamide - Dawei Ni; Wei Xu; Wenli Zhang; Wanmeng Mu (Extremophiles, 2024)

Paracoccus benzoatiresistens sp. nov., a benzoate resistance and selenite reduction bacterium isolated from wetland - Weidong Mu; Haoran Liu; Bai Guo; Kaiyue Wang; Jinhua Hu; Jianjun Song; Xiuyun Li; Shuzhen Wei; Aijv Liu; Hongliang Liu (Antonie van Leeuwenhoek, 2024)

β-arrestin2 promotes angiogenesis of liver sinusoidal endothelial cells through the VEGF/VEGFR2 pathway to aggravate cirrhosis - Feng Gao; Wei Mu; Jiangbo Fan; Jing Shen (Toxicology Letters, 2024)

Which emerging micropollutants deserve more attention in wastewater in the post-COVID-19 pandemic period? Based on distribution, risk, and exposure analysis - Xinhui Xia; Huizhi Mu; Yaqun Li; Yanlong Hou; Jianju Li; Zixuan Zhao; Qingliang Zhao; Shijie You; Liangliang Wei (Science of The Total Environment, 2024)

Biocontrol efficacy and mechanism of endophytic Bacillus velezensis HE-23 from Aucklandia lappa roots against the gray mold of postharvest tomato - Wei Jian; Yu Chen; Shiyu Liu; Xiaogang Ou; Lixinyu Sun; Huiming Gong; Qiutong Mu; Zhengguo Li; Zhengwu Zhao (Postharvest Biology and Technology, 2024)

NHX5/NHX6/SPY22 complex regulates BRI1 and brassinosteroid signaling in Arabidopsis - Jun Shang; Guoxiu Mu; Yuting Qi; Xiao Zhang; Wei Shen; Yujie Xie; Mingrui Ge; Yu He; Feng Qiao; Quan-Sheng Qiu (Journal of Plant Physiology, 2024)

An overview of cyclodextrin on the detection and removal of mycotoxin: Recent advances and future prospects - Yan Shi; Wei Xu; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Control, 2024)

A synergetic binary system of waste cooking oil-derived bio-based surfactants and its interfacial performance for enhanced oil recovery - Ming-Yue Liang; Chi Ma; Wan-Qi Qin; Homely Isaya Mtui; Wei Wang; Jin-feng Liu; Shi-Zhong Yang; Bo-Zhong Mu (Colloids and Surfaces C: Environmental Aspects, 2024)

Multimodal spatiotemporal drug assessment platform based on a microelectrode neural network chip in Alzheimer’s disease - Fan Gao; Wei Xu; Yan Xiao; Wei Jiang; Mu Chen; Zekai Liu; Peng Zhang; Tianyi Yang; Zhiyu Qian; Keqiang Gao (Chemical Engineering Journal, 2024)

Improving the activity of an inulosucrase by rational engineering for the efficient biosynthesis of low-molecular-weight inulin - Dawei Ni; Zhaolin Huang; Shuqi Zhang; Yang Yang; Xiaoyong Liu; Wei Xu; Wenli Zhang; Wanmeng Mu (Archives of Microbiology, 2024)

Recent developments of mycotoxin-degrading enzymes: identification, preparation and application - Yan Shi; Binbin Ouyang; Yulei Zhang; Wenli Zhang; Wei Xu; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Mechanism underlying the role of integrin α3β1 in adhesive dysfunction between thyroid cells induced by diesel engine exhaust particles - Xiaoyin Guo; Siying Tang; Yanting Li; Chaohui Mu; Hongna Zhang; Qixiao Jiang; Menghui Jiang; Wei Han; Yuxin Zheng; Jinmei Piao (Science of The Total Environment, 2024)

Tetracycline degradation by peroxydisulfate activated with the composite material of biochar and cobalt-modified carbon nitride: Efficiency, stability, and degradation pathway - Jie Cao; Xiaoling Shan; Ling Ding; Zhenming Zhang; Xujun Liang; Zhenguo Chen; Guiting Mu; Wei Guo; Xuetao Guo (Journal of Environmental Chemical Engineering, 2024)

High-temperature carbonization synthesis of coal fly ash/chitosan-carbon composite electrodes for enhanced uranium electroadsorption - Jianfeng Zhang; Mu You; Yijun Wei; Mai Xu; Yunhu Hu (Journal of Environmental Chemical Engineering, 2024)

Uncovering the microbial community structure and physiological profiles of terrestrial mud volcanoes: A comprehensive metagenomic insight towards their trichloroethylene biodegradation potentiality - Aslia Asif; Suprokash Koner; Jung-Sheng Chen; Ashiq Hussain; Shih-Wei Huang; Bashir Hussain; Bing-Mu Hsu (Environmental Research, 2024)

Bovine serum albumin-based hydrogels: Preparation, properties and biological applications - Changxin Shi; Shubin Li; Chao Li; Hanyu Liu; Zhanyue Wang; Yihang Li; Mo Li; Xiangxiang Zhang; Wei Mu; Xiaojun Han (Chemical Engineering Journal, 2024)

Structural characterisation and anti-colon cancer activity of an arabinogalactan RSA-1 from Raphani semen - Qi Li; Shuang Jiang; Qianbo Wang; Jiahui Sun; Zhibin Wang; Xiaotong Wang; Xuepeng Shi; Yuanqiu Mu; Lin Wei; Chunjuan Yang (Carbohydrate Polymers, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Bio-refinery of palm kernel expeller waste into attached microalgal biodiesel, the life cycle analysis of waste biomass-to-energy - Hemamalini Rawindran; Kuan Shiong Khoo; Ratchaprapa Raksasat; Chin Seng Liew; Wai Hong Leong; M. Devendran; Balasubramani Ravindran; Woei-Yenn Tong; Jin Chung Sin; Sze Mun Lam; Mu. Naushad; Jun Wei Lim (Process Safety and Environmental Protection, 2024)

Advancements and prospects in the utilization of metal ions and polymers for enhancing aerobic granulation during industrial effluent treatment and resource recovery - Ahmad Hussaini Jagaba; Dahiru U. Lawal; Ismail Abdulazeez; Ibrahim Mohammed Lawal; Nuhu Dalhat Mu'azu; Abdullahi Haruna Birniwa; Abdullahi Kilaco Usman; Haithm Salah Hagar; Nura Shehu Aliyu Yaro; Azmatullah Noor; Kunmi Joshua Abioye; Jun Wei Lim; et al. (Journal of Water Process Engineering, 2024)

Implications of ocean warming and acidification on heavy metals in surface seawater of the Bohai Sea - Yuqiu Wei; Lun Song; Yuanqing Ma; Jiandong Mu; Wei Yi; Jun Sun; Keming Qu; Zhengguo Cui (Journal of Hazardous Materials, 2024)

Synthesis of Iron-Tailing-Based porous ceramic granules for the adsorption of phenol-containing wastewater degradation - Yu Wei; Xue-fei Lei; Shao-hua Luo; Huan-huan Chen; Wen-ning Mu; Fei Teng; Kuo Sun; Shengxue Yan (Journal of Cleaner Production, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Identification and application of a novel patulin degrading enzyme from Cyberlindnera fabianii - Chenyu Song; Wei Xu; Cuie Guang; Ting Xue; Wanmeng Mu (Food Research International, 2024)

Nickel augmented biochar for sustaining produced water treatment to decarbonize oil and gas industrial waste using anaerobic-aerobic granular cylindrical periodic discontinuous batch reactors - Ahmad Hussaini Jagaba; Dahiru U. Lawal; Mohamed A. Yassin; Ismail Abdulazeez; Nuhu Dalhat Mu'azu; Abdullahi Kilaco Usman; Jun Wei Lim; Isam H. Aljundi (Environmental Research, 2024)

A systematic investigation of PVDF-HFP in perovskite solar cells for improved space mission reliability - Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Pei-Yu Chen; Ting-Han Lin; Kun-Mu Lee (Chemical Engineering Journal, 2024)

A review on the application of biochar as an innovative and sustainable biocarrier material in moving bed biofilm reactors for dye removal from environmental matrices - Ahmad Hussaini Jagaba; Ismail Abdulazeez; Dahiru U. Lawal; Augustine Chioma Affam; Nuhu Dalhat Mu’azu; Usman Bala Soja; Abdullahi Kilaco Usman; Azmatullah Noor; Jun Wei Lim; Isam H. Aljundi (Environmental Geochemistry and Health, 2024)

Bioaccumulation mediated by water solubility leads to differences in the acute toxicity of organophosphorus insecticides to zebrafish (Danio rerio) - Yujuan Liu; Yue Xu; Bingjie Yuan; Bingyu Zhu; Xiaobing Zhang; Jinyin Chen; Beixing Li; Wei Mu (Ecotoxicology, 2024)

Neuroprotective Effects of Metformin on Cerebral Ischemia-Reperfusion Injury: Modulation of JNK and p38 MAP Kinase Signaling Pathways - Shicun Zhang; Wei Zou; Yan Leng; Zhuang Mu; Lan Zhan (Cell Biochemistry and Biophysics, 2024)

Glycosylation of flavonoids by sucrose- and starch-utilizing glycoside hydrolases: A practical approach to enhance glycodiversification - Yuqing Tian; Wei Xu; Cuie Guang; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Comprehensive insights into the impact of magnetic biochar on protein hydrolysis in sludge anaerobic digestion: Protein structures, microbial activities and syntrophic metabolisms - Likui Feng; Huizhi Mu; Zhelu Gao; Tianyi Hu; Shufei He; Yu Liu; Shijie You; Qingliang Zhao; Liangliang Wei (Water Research, 2024)

Analysis of microbial community succession and its metabolic characteristics in the first and second rounds of cave-brewed sauce-flavor Baijiu - Tianxing Zou; Yingchun Mu; Qi Qi; Tingting Ren; Wei Su (Food Bioscience, 2024)

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

TAG encodes an adenine nucleotide transport protein that regulates leaf color in rice - Xinfang Zhang; Wenwen Xiao; Mi Wei; Ruhui Wu; Jinyan Liu; Jing You; Jianyan Mu; Jichao Zhang; Yanling Yang; Yitao Wan; Yinghua Lin; Guanghua He; et al. (Euphytica, 2024)

Effects of miR-204-5p and Target Gene EphB2 on Cognitive Impairment Induced by Aluminum Exposure in Rats - Wei Liu; Jie Gao; Niping Hao; Jing Li; Jing Pei; Danfeng Zou; Shuo Yang; Yuhua Yin; Xiaoming Yang; Ping Mu; Lifeng Zhang (Biological Trace Element Research, 2024)

Cryoablation with KCl Solution Enhances Necrosis and Apoptosis of HepG2 Liver Cancer Cells - Mu Chen; Wei Liu; Baolin Liu (Annals of Biomedical Engineering, 2024)

Low-calorie bulk sweeteners: Recent advances in physical benefits, applications, and bioproduction - Jin Li; Quanyu Dai; Yingying Zhu; Wei Xu; Wenli Zhang; Yeming Chen; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2024)

Recent advances in discovery, protein engineering, and heterologous production of ketose 3-epimerase for rare sugar biosynthesis - Jiajun Chen; Dawei Ni; Wei Xu; Wenli Zhang; Wanmeng Mu (Trends in Food Science & Technology, 2024)

The escalating threat of human-associated infectious bacteria in surface aquatic resources: Insights into prevalence, antibiotic resistance, survival mechanisms, detection, and prevention strategies - Aslia Asif; Jung-Sheng Chen; Bashir Hussain; Gwo-Jong Hsu; Jagat Rathod; Shih-Wei Huang; Chin-Chia Wu; Bing-Mu Hsu (Journal of Contaminant Hydrology, 2024)

Exploring the biogeography, morphology, and phylogeny of the condylostomatid ciliates (Alveolata, Ciliophora, Heterotrichea), with establishment of four new Condylostoma species and a revision including redescriptions of five species found in China - Yong Chi; Fan Wei; Danxu Tang; Changjun Mu; Honggang Ma; Zhe Wang; Khaled A. S. Al-Rasheid; Hunter N. Hines; Xiangrui Chen (Marine Life Science & Technology, 2024)
Species of the ciliate class Heterotrichea Stein, 1859 are a cosmopolitan group of unicellular eukaryotic microorganisms, many of which have been widely used as models in various fields of research such as regenerative biology, functional ecology, environmental toxicology, and symbiotic behavior. However, species identification in the heterotrich family Condylostomatidae, especially the most species-rich and type genus Condylostoma Bory de Saint-Vincent, 1824, remains challenging due to incomplete original descriptions, few reliable distinguishing characters, and overlapping features between different species. This study presents an updated revision of Condylostoma and its related genus Condylostomides da Silva Neto, 1994 based on descriptions of five species, including nine populations collected from China, using both morphological and molecular methods. The main findings are as follows: (1) 43 nominal species and about 130 populations are reviewed, resulting in the recognition of 30 valid species of Condylostoma and eight valid species of Condylostomides ; (2) keys, synonyms, biogeographic distributions and amended/improved diagnoses of all valid species are provided; (3) based on the available data, four new Condylostoma species ( C. marinum sp. nov., C. petzi sp. nov., C. villeneuvei sp. nov., and C. microstomum sp. nov.), one new combination ( Condylostomides minimus (Dragesco, 1954) comb. nov. & nom. corr.), and two corrected names ( Condylostoma ancestrale Villeneuve-Brachon, 1940 nom. corr. and Condylostomides nigrus (Dragesco, 1960) nom. corr.) are suggested; (4) cryptic species are detected and proposed for the first time to form the Condylostoma curvum species complex; (5) three highly confusing Condylostoma species, C. kris , C. spatiosum , and C. minutum , are redefined for the first time based on modern taxonomic methods; (6) a ‘flagship’ species, Condylostomides coeruleus , is recorded for the first time from the continent of Asia, substantially expanding its biogeography; (7) ciliature adjacent to the distal end of the paroral membrane within the family Condylostomatidae is uniformly defined as frontal membranelles and is classified into three patterns according to the arrangement of kinetosomes, which serve as important key features.

Enhancing the Stability of Small Rescue Boats: A Study on the Necessity and Impact of Hydraulic Interconnected Suspensions - Xiaochun Mu; Hongwang Du; Wenchao Wang; Wei Xiong (Journal of Marine Science and Engineering, 2024)
Aiming to solve the problem that existing small rescue boats cannot realize the effective and stable rescue of human lives under high sea turbulence conditions, this paper proposes a parallel decoupled hydraulic interconnected suspension system for actual sea state. The system dynamics model is established, and its damping characteristics are analyzed by joint simulation. The results show that compared with the truss-type rescue ship, the suspension system can improve the transverse rocking resistance by 81.5% and the longitudinal rocking resistance by 25.0%, and the system has excellent transverse rocking resistance.

Synergistic developmental effects of zebrafish exposed to combined perfluorooctanoic acid and atrazine - Xiaoyu Zhao; Beinan Wang; Xiao Song; Linjuan He; Wei Zhang; Yongzhong Qian; Xiyan Mu; Jing Qiu (Chemosphere, 2024)

Environmental and human history in the hyper-arid eastern Tarim Basin (Lop Nur), northwest China: A critical review for sustaining the natural and cultural landscapes - Kangkang Li; Xiaoguang Qin; Bing Xu; Lei Zhang; Guijin Mu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Hongjuan Jia; Zhiqiang Yin; et al. (Quaternary International, 2024)

Pressure/temperature-assisted crystallographic engineering–A strategy for developing the infrared phosphors - Yi-Ting Tsai; Tadeusz Leśniewski; Natalia Majewska; Mikołaj Kamiński; Justyna Barzowska; En-Pei Liu; Wei-Tin Chen; Sebastian Mahlik; Mu-Huai Fang (Chemical Engineering Journal, 2024)

The positive effect of the enzyme inducer (MnSO4) on the formation of humic substance in rice straw composting by stimulating key microorganisms - Linying Mu; Runshi Dong; Jiaqi Wang; Jieyu Yue; Lina Pan; Caihong Song; Zimin Wei (Science of The Total Environment, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Separation of rhenium(VII) from nuclear wastewater using N-methyl-glucosamine functionalized exchange resin - Wanjun Mu; Ning Wang; Yalin Huang; Hongyuan Wei (Journal of Water Process Engineering, 2024)

Optimizing the deployment of LID facilities on a campus-scale and assessing the benefits of comprehensive control in Sponge City - Xianbao Zha; Wei Fang; Wei Zhu; Shuangtao Wang; Yong Mu; Xiaofeng Wang; Pingping Luo; Mohd Remy Rozainy Mohd Arif Zainol; Mohd Hafiz Zawawi; Khai Lin Chong; Apip Apip (Journal of Hydrology, 2024)

Long-term exposure to major constituents of fine particulate matter and neurodegenerative diseases: A population-based survey in the Pearl River Delta Region, China - Qi-Zhen Wu; Hui-Xian Zeng; John Andersson; Anna Oudin; Katja M. Kanninen; Mu-Wu Xu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Mei Zheng; Nanxiang Jin; Wei-Chun Chou; et al. (Journal of Hazardous Materials, 2024)

A review of fructosyl-transferases from catalytic characteristics and structural features to reaction mechanisms and product specificity - Wei Xu; Xiaoqi Zhang; Dawei Ni; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Chemistry, 2024)

Landsat observations of total suspended solids concentrations in the Pearl River Estuary, China, over the past 36 years - Qiang Sun; Wei Luo; Xianzhang Dong; Shaohua Lei; Meng Mu; Shuai Zeng (Environmental Research, 2024)

Greenhouse gas emission characteristics during kitchen waste composting with biochar and zeolite addition - Xinyu Geng; Hongyu Yang; Wenfang Gao; Jieyu Yue; Daichen Mu; Zimin Wei (Bioresource Technology, 2024)

A hybrid approach of anaerobic digestion model no. 1 and machine learning to model and optimize continuous anaerobic digestion processes - Yadong Ge; Junyu Tao; Zhi Wang; Lan Mu; Wei Guo; Zhanjun Cheng; Beibei Yan; Yan Shi; Hong Su; Guanyi Chen (Biomass and Bioenergy, 2024)

Mechanism of peroxymonosulfate activation by nanoparticle Co@N–C: Experimental investigation and theoretical calculation - Mu Li; Lin Lin; Wei Zhang; Yubin Zou; Jiahui Hu; Yin Li; Bing Li; Feiyun Sun; Xiao-yan Li (Chemosphere, 2024)

Effect of Maillard reaction based on catechol polymerization on the conversion of food waste to humus - Daichen Mu; Chao Wang; Xinyu Geng; Yue Zhao; Taha Ahmed Mohamed; Di Wu; Zimin Wei (Chemosphere, 2024)

Evaluating groundwater ecosystem dynamics in response to post in-situ remediation of mixed chlorinated volatile organic compounds (CVOCs): An insight into microbial community resilience, adaptability, and metabolic functionality for sustainable remediation and ecosystem restoration - Shih-Wei Huang; Bashir Hussain; Jung-Sheng Chen; Aslia Asif; Bing-Mu Hsu (Science of The Total Environment, 2024)

Performance of microbial inoculation and tricalcium phosphate on nitrogen retention and conversion: Core microorganisms and enzyme activity during kitchen waste composting - Taha Ahmed Mohamed; Zimin Wei; Mohamed Mohaseb; Wu Junqiu; Taha El Maghraby; Xiaomeng Chen; Yousif Abdelrahman Yousif Abdellah; Daichen Mu; Mohamed El Kholy; Chaonan Pan; Ayodeji Bello; Guangren Zheng; et al. (Journal of Environmental Management, 2024)

A ratiometric fluorescence imprinted sensor based on N-CDs and metal–organic frameworks for visual smart detection of malathion - Lidong Yang; Wei Hu; Fubin Pei; Zhiwei Liu; Jiang Wang; Zhaoyang Tong; Xihui Mu; Bin Du; Mingzhu Xia; Fengyun Wang; Bing Liu (Food Chemistry, 2024)

Adsorption of humic acid from different organic solid waste compost to phenanthrene, is fluorescence excitation or quenching? - Xinya Su; Ruju Zhang; Huan Cao; Daichen Mu; Liqin Wang; Caihong Song; Zimin Wei; Yue Zhao (Environmental Pollution, 2024)

Rational synthesis of 1,3,4-thiadiazole based ESIPT-fluorescent probe for detection of Cu2+ and H2S in herbs, wine and fruits - Yu Sun; Jie Mu; Yongchen Wang; Chengwei Lü; Li-Wei Zou (Analytica Chimica Acta, 2024)

Storm surge risk assessment and sensitivity analysis based on multiple criteria decision-making methods: a case study of Huizhou City - Wei Wei; Shining Huang; Hao Qin; Lichen Yu; Lin Mu (Frontiers in Marine Science, 2024)
Coastal areas face escalating storm surge disasters due to rising sea levels and urban growth, posing greater risks to lives and property. Comprehensive storm surge risk assessment and sensitivity analysis in coastal areas are crucial for effective disaster prevention and mitigation. This research focuses on Huizhou, China, conducting a comparative study of storm surge risk assessment and sensitivity analysis based on an integrated approach, which includes the storm surge inundation numerical model (FVCOM-SWAN), Geographic Information System (GIS) and Remote Sensing (RS) techniques, and Multiple Criteria Decision-Making (MCDM) methods. Ten flood-related risk indicators are selected from the hazard, exposure and vulnerability, the weights of which are evaluated through a comprehensive comparison among Analytic Hierarchy Process (AHP), Fuzzy Analytic Hierarchy Process (FAHP), Entropy Weight (EW), AHP-EW, and FAHP-EW methods. High-precision risk level maps are generated subsequently utilizing GIS and RS techniques. Sensitivities of the indicators are analyzed using One-At-A-Time (OAT) and Fourier Amplitude Sensitivity Test (FAST) methods. The proposed storm surge risk assessment framework, the MCDM comparative study and the sensitivity analysis can offer insights for better understanding and management of storm surge risks, and contribute to the standardization and application of storm surge risk assessment.

Repeat dose and reproductive toxicity of thrombopoietin mimic peptide in Sprague-Dawley rats - Shidong Qiu; Yuji Liang; Xiaobo Wang; Xiue Li; Guoyue Wei; Peng Xiao; Suling Teng; Peilu Sun; Lei Song; Zenglin Zhao; Yanling Mu (Regulatory Toxicology and Pharmacology, 2024)

Development of an alternative low-cost culture medium for a new isolated high-production DHA strain using kitchen wastewater - Qing Wang; Wenbiao Jin; Yujia Qin; Xu Zhou; Wei Han; Shuhong Gao; Xuan Li; Mu. Naushad; Guangming Jiang; Huan Liu (Process Safety and Environmental Protection, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Microbial dextran-hydrolyzing enzyme: Properties, structural features, and versatile applications - Ziwei Chen; Jiajun Chen; Dawei Ni; Wei Xu; Wenli Zhang; Wanmeng Mu (Food Chemistry, 2024)

Production, effects, and applications of fructans with various molecular weights - Dawei Ni; Shuqi Zhang; Xiaoyong Liu; Yingying Zhu; Wei Xu; Wenli Zhang; Wanmeng Mu (Food Chemistry, 2024)

Identification and application of a novel deoxynivalenol-degrading enzyme from Youhaiella tibetensis - Yan Shi; Wei Xu; Dawei Ni; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Chemistry, 2024)

Life-cycle analysis of biohydrogen production via dark-photo fermentation from wheat straw - Mingjie Jin; Xuan Wei; Xuefang Mu; Weixi Ren; Sihu Zhang; Canfang Tang; Wen Cao (Bioresource Technology, 2024)

A bibliometric assessment of the science and practice of blue–green space (BGS): hot spots, lacunae, and opportunities - Bo Mu; Ruting Zhao; Yang Liu; Enkai Xu; Yali Zhang; Hong Wei; Guohang Tian (Socio-Ecological Practice Research, 2024)

Identification of sources and analysis of spatial distribution of soil heavy metals in northern China coal mining areas - Xiaojing Zhang; Shengwei Zhang; Xiaoyan Wei; Zhiqiang Liu; Chunxue Wang; Hongying Mu; Yuzhe Han; Chengxu Liu (Environmental Geochemistry and Health, 2024)

Niche-specific modulation of long-chain n-alkanes degrading bacterial community and their functionality in forest habitats across the leaf litter-soil compartments - Bashir Hussain; Jung-Sheng Chen; Bing-Mu Hsu; Wei-Chun Chao; Cheng-Wei Fan (Applied Soil Ecology, 2024)

Capturing spatiotemporal heterogeneity in fertilizer application for better modelling paddy water nitrogen and phosphorus pollution at regional scale - Rui Ren; Huazhan Zhang; Xiang Gao; Housheng Wang; Wei Jiang; Yuhui Wang; Xiaosan Jiang; Zhaofu Li; Haiyan Zhao; Ganghua Li; Yanfeng Ding; Yue Mu (Agriculture, Ecosystems & Environment, 2024)

Recent progress in health effects and enzymatic production of epilactose, a functional lactose derivative - Suchun Xiong; Zhaolin Huang; Wei Xu; Junmei Ding; Dawei Ni; Wanmeng Mu (Trends in Food Science & Technology, 2024)

Integrated control strategy for dual sludge ages in the high-concentration powder carrier bio-fluidized bed (HPB) technology: Enhancing municipal wastewater treatment efficiency - Chengxian Wang; Xiaoli Chai; Bin Lu; Wei Lu; Hongbo Han; Yue Mu; Qun Gu; Boran Wu (Journal of Environmental Management, 2024)

Improving thermostability, solvent tolerance, and reusability of methyl parathion hydrolase through immobilization into the metal-organic framework ZIF-8 - Wei Xu; Minwen Sun; Wenli Zhang; Cuie Guang; Wanmeng Mu (Food Bioscience, 2024)

Pilot-scale removal of PFAS from chromium-plating wastewater by anion exchange resin and activated carbon: Adsorption difference between PFOS and 6:2 fluorotelomer sulfonate - Xiangzhe Jiang; Ziming Zhou; Dongsheng Wang; Guocheng Liu; Wei Wang; Shuang Mu; Gang Yu; Shubo Deng (Chemical Engineering Journal, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

A New Plastic Design Approach for the Vertical-Side-Plating Thickness of Ice-Strengthened Ships Suffering from Ice Floe Impacts - Mengying Mu; Kailing Guo; Wei Cai; Ling Zhu; Zhenyu Pi; Shuo Zhou (Journal of Marine Science and Engineering, 2024)
Ice-strengthened ships inevitably suffer from ice floe impacts during navigation in icy regions. Under some extreme-ice-impact loadings, the ship structure will experience plastic deformations. The magnitude of plastic deformation is highly correlated with the ice floe-impact energy level. During most ice impacts, only the ship’s plate undergoes minor plastic deformation. Considering that the structure still has a high structural strength with a minor permanent deformation, developing a structural plastic design method for polar ships has become a hot research issue in current studies. Therefore, in this paper, based on the rigid-plastic theory and the ice-crushing-energy approach, an experimentally verified theoretical model for predicting plastic deformations of the vertical-side plate of polar ship subjected to ice floe impacts was established. According to the analytical solutions of the plastic deformation, the plastic design formula to determine the plating thickness of ice-strengthened ships subjected to ice floe impacts was further derived based on the plastic design criteria. In addition, the parameter analysis of ice strength described by the ice pressure–area relationship, allowable-permanent-set parameter, impact energy and ice shape were conducted, and plating-thickness design curves with different design parameters were given. The design of plating thickness is very sensitive to the determinations of the allowable-permanent set and ice pressure–area curves. The designed plating thickness decreased with the increase of the allowable-permanent set. Moreover, a comparative analysis of the designed plating thickness for ice floe impact and rigid-mass impact was also carried out. Under the same impact conditions, due to energy absorption caused by ice damage, the designed thickness of the plate for rigid-mass impact was much larger than that for the ice impact. It is necessary to consider the impact-induced ice damage and energy dissipation in a structural design, instead of using rigid impact loads for conservative design. The research in this paper can provide some useful references for the structural design of ice-strengthened ships subject to ice floe impacts.

Hydrothermal carbonization of coking sludge: Formation mechanism and fuel characteristic of hydrochar - Jun Zhong; Wei Zhu; Jipeng Sun; Biao Mu; Xin Wang; Zongpu Xue; Jun Cao (Chemosphere, 2024)

A novel Vibrio alginolyticus phage and its therapy application in Portunus trituberculatus larvae - Ruqian Cai; Dengfeng Li; Weinan Qin; Wei Lin; Lingting Pan; Minhua Qian; Fei Wang; Chunlin Wang; Changkao Mu; Yigang Tong (Aquaculture, 2024)

Comparative evaluation of soybean meal vs. extruded soybean meal as a replacer for fishmeal in diets of olive flounder (Paralichthys olivaceus): Effects on growth performance and muscle quality - Nannan Shen; Zhicheng Song; Cancan Xia; Hua Mu; Xiangning Chen; Hanliang Cheng; Jianhe Xu; Yongkai Sun; Chaoqing Wei; Lu Zhang (Aquaculture, 2024)

Exploring the heterogeneity of community and function and correspondence of “species-enzymes” among three types of Daqu with different fermentation peak-temperature via high-throughput sequencing and metagenomics - Ying Huang; Dong Li; Yu Mu; Zhiyu Zhu; Yuzhang Wu; Qi Qi; Yingchun Mu; Wei Su (Food Research International, 2024)

Deoxynivalenol: Occurrence, toxicity, and degradation - Yulei Zhang; Binbin Ouyang; Wenli Zhang; Cuie Guang; Wei Xu; Wanmeng Mu (Food Control, 2024)

A Critical Review of On-Line Oil Wear Debris Particle Detection Sensors - Wenbo Han; Xiaotong Mu; Yu Liu; Xin Wang; Wei Li; Chenzhao Bai; Hongpeng Zhang (Journal of Marine Science and Engineering, 2023)
In the field of marine engineering, the friction and wear experienced by rotating mechanisms are recognized as significant contributors to the failure of marine machinery. In order to enhance the safety and dependability of marine ship operations, the implementation of on-line oil wear debris particle detection sensors enables the on-line monitoring of oil and facilitates the rapid identification of abnormal wear locations. This paper provides a critical review of the recent research progress and development trends in the field of sensors for on-line detection of oil wear debris particles. According to the method of sensor detection, wear debris particle detection sensors can be classified into two distinct categories: electrical and non-electrical sensors. Electrical sensors encompass a range of types, including inductive, capacitive, and resistive sensors. Non-electrical sensors encompass a range of technologies, such as image processing sensors, optical sensors, and ultrasonic sensors. Finally, this review addresses the future research directions for wear debris particle detection sensors in light of the challenging problems currently faced by these sensors.

A multidimensional optimization strategy of pyraclostrobin-loaded microcapsules to improve the selectivity between toxicological risk in zebrafish and efficacy in controlling rice blast - Xueping Huang; Jian Luo; Haichao Cao; Aiping Wang; Fengyan Zhou; Feng Liu; Beixing Li; Wei Mu; Yong Zhang (Science of The Total Environment, 2023)

A sustainable strategy to transform cotton waste into renewable cellulose fiber self-reinforcing composite paper - Chan Wang; Jinhui Su; Taoyuan Liu; Shengbo Ge; Rock Keey Liew; Hui Zhang; Mu Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Wei Fan (Journal of Cleaner Production, 2023)

Improved solid/liquid separation performance of hydrochar from sludge via hydrothermal carbonization - Jun Zhong; Wei Zhu; Biao Mu; Jipeng Sun; Xin Wang; Naixi Lin; Jun Cao (Journal of Environmental Management, 2023)

Low temperature preparation of high-performance citric acid crosslinked starch gels with adjustable properties based on cationic esterification synergistic crosslinking - Wenguang Wei; Min Wu; Nan Shang; Rongyi Mu; Tong Zhang; Huihuang Xu (Food Hydrocolloids, 2023)

An overview of chemical, physical and biological methods for zearalenone elimination: Recent advances and future prospective - Yulei Zhang; Binbin Ouyang; Wenli Zhang; Cuie Guang; Wei Xu; Wanmeng Mu (Food Control, 2023)

Waterborne polyurethanes with novel chain extenders bearing multiple sulfonate groups - Guozheng Xia; Jinkang Hu; Qian Sun; Chi Chen; Xin Wang; Chao Zhu; Wei Jiang; Xiaobo Wan; Youbing Mu (Chemical Engineering Journal, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

High-performance inkjet-printed inverted QD-LEDs based on cross-linkable electron regulation layers - Liming Xie; Qing Li; Yuan-Qiu-Qiang Yi; Gengrui Qiu; Omolola Esther Fayemi; Xinju Mu; Zhongsheng Ma; Pengyu Tang; Yang Liu; Wenming Su; Wei Lei; Zheng Cui (Chemical Engineering Journal, 2023)

Fibrillarin promotes homologous recombination repair by facilitating the recruitment of recombinase RAD51 to DNA damage sites - Yanhua Mu; Jinhua Han; Mingjie Wu; Zongfang Li; Ke Du; Yameng Wei; Mengjie Wu; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2023)

Cerina litoralis gen. nov., sp. nov., a novel potential polysaccharide degrading bacterium of the family Flavobacteriaceae, isolated from marine sediment - Ya-Wei Wang; Xin-Hui Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Antonie van Leeuwenhoek, 2023)

Satellite-observed significant improvement in nearshore transparency of the Bohai Sea during pollution control - Xuyan Li; Jinzhao Xiang; Liudi Zhu; Zhibin Yang; Ting Wei; Bing Mu; Xiaobo Zhang; Tingwei Cui (Acta Oceanologica Sinica, 2023)

Exposure to phthalates and their alternatives in relation to biomarkers of inflammation and oxidative stress in adults: evidence from NHANES 2017–2018 - Shihao Jin; Shanshan Cui; Xiaoyu Mu; Zhao Liu; Yu Han; Tingkai Cui; Wenjuan Xiong; Wei Xi; Xin Zhang (Environmental Science and Pollution Research, 2023)

Residue dissipation dynamics and dietary risk assessment of emamectin benzoate, chlorantraniliprole, chlorfenapyr, and lufenuron in cabbage - Xiaoyao Wang; Shuai Hu; Lingtao Meng; Kai Wang; Xianxia Zhang; Ke Li; Ning Wang; Nan Zou; Yue Xu; Beixing Li; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2023)

Effect mechanism of iron conversion on adsorption performance of hydrochar derived from coking sludge - Jun Zhong; Wei Zhu; Xin Wang; Jipeng Sun; Biao Mu; Yucheng Xu; Guorui Li (Science of The Total Environment, 2023)

Optimizing flow regime for the Four Major Chinese Carps by integrating habitat suitability within reservoir operation - Zehao Lv; Gangsheng Wang; Peng Zhang; Xueshan Ai; Xin Cao; Wei Zheng; Zhenyu Mu; Bowen Yu (Journal of Hydrology, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

Inoculum size-insensitive susceptibility determination of urine sample based on in-situ measurement of inducible enzyme activity after 20 min of antibiotic exposure - Wenshuai Wu; Yuanjie Suo; Qianbin Zhao; Gaozhe Cai; Yang Liu; Wei Jin; Ying Mu; Boran Zhang (Analytica Chimica Acta, 2023)

Bioavailability-based risk assessment of various heavy metals via multi-exposure routes for children and teenagers in Beijing, China - Zhongwen Du; Zuguang Tian; Yelan Yin; Junxiao Wei; Yue Mu; Jianjun Cai; Zefeng Song; Kuang Cen (Environmental Science and Pollution Research, 2023)

Theoretical Analysis of Plastic Behavior of Sandwich Beam with Metal Foam under Repeated Impacts - Kailing Guo; Mengying Mu; Wei Cai; Bofang Xu; Ling Zhu (Journal of Marine Science and Engineering, 2023)
The phenomenon of repeated impacts on engineering structures is very common, especially in naval and ocean engineering. When marine structures are subjected to repeated impact loadings, deformation and damage will accumulate as the impact number increases, resulting in the failure and damage of the structures, even causing serious accidents. Based on the rigid-plastic assumption, a theoretical model is established to analyze the plastic mechanical behavior of metal foam sandwich beams (MFSBs) suffering from repeated impacts, in which the membrane factor method (MFM) is applied to derive analytical solutions for the plastic responses of MFSBs. The theoretical predictions agree well with the results of impact tests and numerical simulations, indicating that the theoretical model is accurate and reliable. In addition, the dynamic responses of MFSBs are analyzed based on the MFM, and the effects of the core strength and the face thickness on the deflection responses are determined. The results show that the dimensionless permanent deflection of MFSBs is sensitive to the core strength ratio and the face thickness ratio, and as the core strength ratio or the face thickness ratio increases, the dimensionless permanent deflection decreases gradually in an exponential form. In addition, the influence of the core strength ratio and face thickness ratio becomes more significant as the impact number increases. The proposed theoretical method can provide a theoretical reference and technical support for the design of metal foam sandwich structures with improved impact resistance under repeated impact loadings.

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

PANI grafted onto waste poros polyurethane for co-adsorption of multiple pollutants in industrial wastewater - Ning Wang; Yirui Guo; Yi Song; Wei Yan; Xuesong Gong; Yunfeng Li; Rui hua Mu; Yonghong Liu; Luohong Zhang (Journal of Water Process Engineering, 2023)

Towards low energy-carbon footprint: Current versus potential P recovery paths in domestic wastewater treatment plants - Qian Zhao; Hao Ying; Yu Liu; Hongbo Wang; Jingtao Xu; Wei Wang; Juan Ren; Shujuan Meng; Ning Wang; Ruimin Mu; Shasha Wang; Jingjing Li (Journal of Environmental Management, 2023)

Improving the yield and tetracycline adsorption performance of kitchen waste biochar through subcritical dimethyl ether pretreatment - Jipeng Sun; Wei Zhu; Jun Cao; Jun Zhong; Biao Mu; Xin Wang; Naixi Lin (Journal of Environmental Chemical Engineering, 2023)

Underpinning the ecological response of mixed chlorinated volatile organic compounds (CVOCs) associated with contaminated and bioremediated groundwaters: A potential nexus of microbial community structure and function for strategizing efficient bioremediation - Bashir Hussain; Jung-Sheng Chen; Shih-Wei Huang; I-Sen Tsai; Jagat Rathod; Bing-Mu Hsu (Environmental Pollution, 2023)

Self-healing polyurethane coatings based on dynamic chemical bond synergy under conditions of photothermal response - Kang Chen; Haoxin Zhu; Zhiyi Zhang; Yingqing Shao; Qianhui Yu; Xinlei Cao; Siyan Pan; Xin Mu; Zhenhua Gao; Di Wang; Shuangying Wei; Shuaiyuan Han (Chemical Engineering Journal, 2023)

Modulating the coordination environment of Co single-atom catalysts through sulphur doping to efficiently enhance peroxymonosulfate activation for degradation of carbamazepine - Wei Zhang; Mu Li; Jingwen Luo; Guan Zhang; Lin Lin; Feiyun Sun; Mei Li; Zijun Dong; Xiao-yan Li (Chemical Engineering Journal, 2023)

Effect of microbial pretreatment on degradation of food waste and humus structure - Daichen Mu; Kexin Ma; Liangzi He; Zimin Wei (Bioresource Technology, 2023)

Dendrobium officinale polysaccharides improved reproductive oxidative stress injury in male mice treated with cyclophosphamide - Yi Mu; Bangwei Che; Kaifa Tang; Wenjun Zhang; Shenghan Xu; Wei Li; Jun He; Miao Liu; Peng Chen; Siwen Zhong; Guangyu Li (Environmental Science and Pollution Research, 2023)

Biological characters identification for hard clam larva based on the improved YOLOX-s - Yaxin Wang; Haiyun Wu; Xiuping Hua; Dongyue Ren; Yang Li; Zhimin Mu; Wei Xu; Yong Wei; Tao Zhang; Yongcheng Jiang (Computers and Electronics in Agriculture, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

D-allulose, a versatile rare sugar: recent biotechnological advances and challenges - Wenli Zhang; Ding Chen; Jiajun Chen; Wei Xu; Qiuming Chen; Hao Wu; Cuie Guang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Temperature and light dependency of isoprene and monoterpene emissions from tropical and subtropical trees: Field observations in south China - Jianqiang Zeng; Yanli Zhang; Zhaobin Mu; Weihua Pang; Huina Zhang; Zhenfeng Wu; Wei Song; Xinming Wang (Applied Geochemistry, 2023)

Maribacter aquimaris sp. nov., isolated from seawater adjacent to Fildes Peninsula, Antarctica - Yanfeng Zhang; Yanwu Zhai; Lulu Mu; Miaomiao Hu; Wei Fang; Yazhong Xiao; Zemin Fang (Antonie van Leeuwenhoek, 2023)

Interactions and quantification of multiple influencing factors on cadmium accumulation in soil-rice systems at a large region - Yue Mu; Jingxin Cui; Andi Liu; Shuai Wang; Qiujun Shi; Jing Wang; Shiqiang Wei; Jinzhong Zhang (Science of The Total Environment, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Cross-sectional and longitudinal relationships between ozone exposure and glucose homeostasis: Exploring the role of systemic inflammation and oxidative stress in a general Chinese urban population - Qiyou Tan; Bin Wang; Zi Ye; Ge Mu; Wei Liu; Xiuquan Nie; Linling Yu; Min Zhou; Weihong Chen (Environmental Pollution, 2023)

Green recovery of Li, Ni, and Mn from spent xLi2MnO3·(1-x)LiMO2 cathode materials: Experimental study and mechanism analysis - Yifan Wang; Qijun Zhang; Xiaoxia Bai; Panpan Mu; Xiaoguang Zhang; Wei Wang; Zhe Tan; Zhenhuan Zhao; De'an Pan (Chemical Engineering Journal, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

In-situ anaerobic treatment removes the passivation layer of sponge iron to restore the nitrogen and phosphorus removal performance of SBR - Kaiyao Hu; Wenxuan Li; Hao Mu; Shuang Ren; Hongjuan Zhu; Kexin Zeng; Bo Wang; Jinming Liang; Qi Zhang; Lili Yang; Wei Zhao; Juqiang Xiao (Process Safety and Environmental Protection, 2023)

Deciphering endemic rhizosphere microbiome community’s structure towards the host-derived heavy metals tolerance and plant growth promotion functions in serpentine geo-ecosystem - Rajendran Senthil Kumar; Suprokash Koner; Hsin-Chi Tsai; Jung-Sheng Chen; Shih- Wei Huang; Bing-Mu Hsu (Journal of Hazardous Materials, 2023)

Metagenomic analysis to determine the characteristics of antibiotic resistance genes in typical antibiotic-contaminated sediments - Han Yang; Mu Xu; Liqing Wang; Xianyun Wang; Erik Jeppesen; Wei Zhang (Journal of Environmental Sciences, 2023)

Engineering D-allulose 3-epimerase from Clostridium cellulolyticum for improved thermostability using directed evolution facilitated by a nonenzymatic colorimetric screening assay - Jiajun Chen; Zhaolin Huang; Ting Shi; Dawei Ni; Yingying Zhu; Wei Xu; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2023)

Comprehensive analysis and identification of the circ_0084615/miR-451a/MEF2D axis in benzo(a)pyrene exposed tumor cells in hepato-carcinogenesis - Wei Mu; Pengfei Gu; Weiwei Song; Tengfei Zhu; Wenbo Wang; Yanfeng Zhou (Food and Chemical Toxicology, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Ecotoxicological risk assessment of 14 pesticides and corresponding metabolites to groundwater and soil organisms using China-PEARL model and RQ approach - Jiangong Jiang; Zhixin Liu; Beixing Li; Shankui Yuan; Ronghua Lin; Xin Yu; Xiao Liu; Xianxia Zhang; Ke Li; Dong Xiao; Shaoli Yu; Wei Mu (Environmental Geochemistry and Health, 2023)

Bamboo-based magnetic activated carbon for efficient removal of sulfadiazine: Application and adsorption mechanism - Fan Yang; Can Jin; Sen Wang; Yujie Wang; Lu Wei; Longhui Zheng; Haiping Gu; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Chemosphere, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

Analysis of oil synthesis pathway in Cyperus esculentus tubers and identification of oleosin and caleosin genes - Youcheng Zhu; Ying Wang; Zunmiao Wei; Xiaokai Zhang; Bingyang Jiao; Yu Tian; Fan Yan; Jingwen Li; Yajing Liu; Xuguang Yang; Jinhao Zhang; Xinyue Wang; et al. (Journal of Plant Physiology, 2023)

Value-added utilization of hydroxy-substituted aromatics in coal-derived liquids - Zhi-Hao Ma; Sheng Li; Xue-Qian Dong; Cai-Xia Ju; Dan Mu; Zheng Yang; Min Li; Xian-Hou Guo; Zhi-Min Zong; Xing-Shun Cong; Xian-Yong Wei (Fuel, 2023)

Organic matter accumulation mechanisms in the Wufeng-Longmaxi shales in western Hubei Province, China and paleogeographic implications for the uplift of the Hunan-Hubei Submarine high - Shizhen Li; Zhi Zhou; Haikuan Nie; Mu Liu; Fanyang Meng; Bin Shen; Xiaotao Zhang; Siyu Wei; Zhaodong Xi; Shousong Zhang (International Journal of Coal Geology, 2023)

Modification of sedimentation and bioaccumulation behavior as an efficient strategy to modulate the toxicity of pyraclostrobin to zebrafish (Danio rerio) - Aiping Wang; Yue Sun; Zhengyi Sun; Xiao Liu; Xin Yu; Ke Li; Xianxia Zhang; Yue Xu; Wei Mu; Beixing Li (Environmental Pollution, 2023)

Applicability analysis of thermosyphon for thermally stabilizing pipeline foundation permafrost and its layout optimization - Fei Wang; Guoyu Li; Fedorov Alexander; Wei Ma; Dun Chen; Gang Wu; Yanhu Mu; Xinbin Wang; Hongyuan Jing; Zhenrong Zhang (Cold Regions Science and Technology, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Controllable assembly of three-dimensional porous graphene-Au dual aerogels and its application for high-efficient bioelectrocatalytic O2 reduction - Tuotuo Ma; Wenjing Mu; Yarui Tang; Wenhua Bi; Wei Liu; Dan Wen (Analytica Chimica Acta, 2023)

Chemical contaminants from food contact materials and articles made from or containing wood and bamboo – a review - Mu-Ying Guan; Huai-Ning Zhong; Zhi-Wei Wang; Wen-Wen Yu; Chang-Ying Hu (Food Additives & Contaminants: Part A, 2023)

Artificial intelligence-aided preparation of perovskite SrFexZr1-xO3-δ catalysts for ozonation degradation of organic pollutant concentrated water after membrane treatment - Xu Wang; Yanan Zhang; Cheng Zhang; Huangzhao Wei; Haibo Jin; Zhao Mu; Xiaofei Chen; Xinru Chen; Ping Wang; Xiaoyan Guo; Fuchen Ding; Xiaowei Liu; et al. (Chemosphere, 2023)

Varying abundance of microplastics in tissues associates with different foraging strategies of coastal shorebirds in the Yellow Sea - Wei Liu; Xiaomei Chen; Ting Liang; Tong Mu; Yanzhe Ding; Yan Liu; Xiaoshou Liu (Science of The Total Environment, 2023)

Nonlinear investigation of laterally loaded piles in layered sand with a modified conical strain wedge model - Xun Zhang; Zhiping Hu; Linlong Mu; Wei Tian; Yaguo Zhang; Pei Huang (Ocean Engineering, 2023)

Quantitative proteomics study on the changes of egg white of yellow preserved primary chicken eggs soaked in alkali solution - Denghui Shi; Wei Su; Yingchun Mu (Food Research International, 2023)

Analysis of the formation mechanism of volatile and non-volatile flavor substances in corn wine fermentation based on high-throughput sequencing and metabolomics - Tianyan Chen; Hanyu Wang; Wei Su; Yingchun Mu; Yexin Tian (Food Research International, 2023)

Effects of Pediococcus acidilactici and Rhizopus Oryzae on microbiota and metabolomic profiling in fermented dry-cure mutton sausages - Li Jiang; Yingchun Mu; Wei Su; Haiyong Tian; Mouming Zhao; Guowan Su; Chi Zhao (Food Chemistry, 2023)

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Drought trigger thresholds for different levels of vegetation loss in China and their dynamics - Wenwen Guo; Shengzhi Huang; Qiang Huang; Guoyong Leng; Zhenxia Mu; Zhiming Han; Xiaoting Wei; Dunxian She; Hanye Wang; Zhixia Wang; Jian Peng (Agricultural and Forest Meteorology, 2023)

Flavobacterium potami sp. nov., a multi-metal resistance genes harbouring bacterium isolated from shallow river silt - Shucheng Li; Sidi Mao; Weidong Mu; Bai Guo; Chen Li; Qing Zhu; Xiaoxiao Hou; Yanfang Zhao; Shuzhen Wei; Hongliang Liu; Aiju Liu (Antonie van Leeuwenhoek, 2023)

Design and experiment of cone disk centrifugal shellfish seeding device - Hanbing Zhang; Pengpeng Li; Haonan Zhang; Wei Huang; Guochen Zhang; Gang Mu; Xiuchen Li (Frontiers in Marine Science, 2023)
This paper designed a centrifugal shellfish seeding device with a conical disc structure to improve the seeding efficiency and uniformity of the centrifugal shellfish seeding device. The dynamic model of the shellfish seedling moving on the conical disk is established, and the main parameters affecting the shellfish seedling’s movement characteristics are determined as the cone angle of the impeller, the speed of the impeller, and the offset angle of the blade. Using the EDEM software and the shellfish seedlings blanking rate as the influencing factors, a single factor simulation test was performed. The research found that the variation trend of shellfish seedlings distribution in a single statistical area gradually decreased along the horizontal direction of both sides, with the origin being the center of the seedling sowing device. Test orthogonal rotation simulations using the variation coefficient of seedlings distribution uniformity and the effective job width as evaluation indicators. Use Design Expert software to optimize the structure of the seedling sowing device based on the test results, and determine the optimal structure with the maximum width and the minimum variation coefficient as constraints: the impeller cone angle is 7.72°, and the blade offset angle is -0.9°. Use the above-mentioned seeding device for simulation and actual seeding testing. The simulation results show that when the impeller speed is 750r/min and the blanking rate is 0.65kg/s, the variation coefficient of seedlings distribution uniformity and the effective job width are 12.84% and 24.98m, respectively, while the actual test results are 13.77% and 23.25m, respectively. The object of the seeding performance test was commonly used size shellfish seedlings of the Philippines clam. The results showed that the impeller speed, blanking rate, quadratic term of shellfish seedling size, quadratic term of blanking rate, and interactive term of impeller speed and blanking rate had significant effects on the variation coefficient of the distribution uniformity of shellfish seedlings ( P <0.01). Shellfish seedling size, impeller speed, and interactive term of impeller speed and blanking rate all had a significant impact on job width ( P <0.01). The results of this study provide a reference for the mechanized design of shellfish seeding.

A novel bioelectrochemical strategy for efficient treatment of saline-alkaline and oligotrophic sulfate wastewater mediated by bacterial electron shuttling - Hongyan Shen; Zhitao Zhang; Zheng Chen; Jiachang Shen; Qifeng Wen; Yunpu Jia; Chenxi Yu; Gaojie Wei; Tingzhen Mu; Delu Miao; Maohua Yang; Jianmin Xing (Journal of Water Process Engineering, 2023)

Considering spatio-temporal dynamics of soil water with evapotranspiration partitioning helps to clarify water utilization characteristics of summer maize under deficit irrigation - Jiatun Xu; Qing Mu; Yibo Ding; Shikun Sun; Yufeng Zou; Lianyu Yu; Pengyan Zhang; Nan Yang; Wei Guo; Huanjie Cai (Journal of Hydrology, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Humic acid nature and compound structure together determine the capacity of soil to sorb Avermectin B1a and its derivatives - Tong-fang Jing; Da-xia Zhang; Yan Jin; Guo-dong Si; Bei-xing Li; Wei Mu; Feng Liu (Chemical Engineering Journal, 2023)

Indole acetylated high-amylose maize starch: Synthesis, characterization and application for amelioration of colitis - Yingying Song; Xinyan Qu; Mei Guo; Qiongzheng Hu; Yan Mu; Na Hao; Yunbo Wei; Quanbo Wang; Charles R. Mackay (Carbohydrate Polymers, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Influence of ionized saline water on soil water and salt transport in saline soils - Kai Wei; Shudong Lin; Jihong Zhang; Quanjiu Wang; Yi Guo; Weiyi Mu (Irrigation and Drainage, 2023)
The utilization of saline water plays an important role in agricultural production in saline areas to overcome freshwater shortages. Ionized saline water might alleviate the adverse effects of salinity on soil and plants. In this study, field experiments were conducted to study the effect of ionized saline water on the soil water content and salinity distribution in a sandy soil under a surface emitter. Passing groundwater through an ionization system installed on a feeding pipeline resulted in producing ionized saline water. Three emitter discharges (1.0, 1.8, 3.1 L h −1 ) and two water types (non‐ionized and ionized saline water) were considered in the experiments. As a result of using ionized saline water, soil water content and salt leaching increased. Ionized treatment increased the salinity desalination rate by 31, 33 and 26% for surface soil layer in comparison with non‐ionized treatments of 1.0, 1.8 and 3.1 L h −1 , respectively. It was found that using ionized saline water could decrease the surface wetting radius by 6–9% and increase the wetting depth by 11–17%. A discharge rate of 1.8 L h −1 was recommended as the optimal discharge rate for ionized saline water under drip irrigation. The results indicated that saline water could be improved through ionized treatment for agricultural irrigation in saline soils in an arid region.

Phytoplankton community structure in the Western Subarctic Gyre of the Pacific Ocean during summer determined by a combined approach of HPLC-pigment CHEMTAX and metabarcoding sequencing - Quandong Xin; Xiaohan Qin; Guannan Wu; Xiaokun Ding; Xinliang Wang; Qingjing Hu; Changkao Mu; Yuqiu Wei; Jufa Chen; Tao Jiang (Frontiers in Marine Science, 2023)
The Western Subarctic Gyre (WSG) is a cyclonic upwelling gyre in the northwest subarctic Pacific, which is a region with a high concentration of nutrients but low chlorophyll. We investigated the community structure and spatial distribution of phytoplankton in this area by using HPLC-pigment CHEMTAX (a chemotaxonomy program) and metabarcoding sequencing during the summer of 2021. The phytoplankton community showed significant differences between the two methods. The CHEMTAX analyses identified eight major marine phytoplankton assemblages. Cryptophytes were the major contributors (24.96%) to the total Chl a , followed by pelagophytes, prymnesiophytes, diatoms, and chlorophytes. The eukaryotic phytoplankton OTUs obtained by metabarcoding were categorized into 149 species in 96 genera of 6 major groups (diatoms, prymnesiophytes, pelagophytes, chlorophytes, cryptophytes, and dinoflagellates). Dinoflagellates were the most abundant group, accounting for 44.74% of the total OTUs obtained, followed by cryptophytes and pelagophytes. Sixteen out of the 97 identified species were annotated as harmful algal species, and Heterocapsa rotundata , Karlodinium veneficum , and Aureococcus anophagefferens were assigned to the abundant group (i.e., at least 0.1% of the total reads). Nutrients were more important in shaping the phytoplankton community than temperature and salinity. The 24 stations were divided into southern and northern regions along 44°N according to the k -means method, with the former being dominated by high Chl a and low nutrients. Although different phytoplankton assemblages analyzed by the two methods showed various relationships with environmental factors, a common feature was that the dinoflagellate proportion showed a significantly negative correlation with low nutrients and a positive correlation with Chl a .

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Exposure of zebrafish (Danio rerio) to trans-2-hexenal induces oxidative stress and protein degeneration of the gill - Dicheng Ma; Haiyan Yu; Guangrui Cui; Jiamei Zhu; Bingyu Zhu; Wei Mu; Feng Liu (Science of The Total Environment, 2023)

Experimental investigation on the mooring dynamics of the flexible trash intercept net under wave-current combined actions - Mingxiao Xie; Shan Li; Yu Mu; Yanjie Wei; Tiaojian Xu; Zhenxiang Sun; Chunguang Yuan (Ocean Engineering, 2023)

Short-term microbial effects on n-alkane during the early phase degradation and consequential modification of biomarkers in a lowland subtropical rainforest in southern Taiwan: A litterbag experiment - Bing-Mu Hsu; Jung-Sheng Chen; Tung-Yi Huang; Bashir Hussain; Wei-Chun Chao; Cheng-Wei Fan (Journal of Environmental Management, 2023)

Effects of Jiuqu inoculating Rhizopus oryzae Q303 and Saccharomyces cerevisiae on chemical components and microbiota during black glutinous rice wine fermentation - Chi Zhao; Wei Su; Yingchun Mu; Lixin Luo; Mouming Zhao; Shuyi Qiu; Guowan Su; Li Jiang (International Journal of Food Microbiology, 2023)

Performance and mechanisms for tetrabromobisphenol A efficient degradation in a novel homogeneous advanced treatment based on S2O42− activated by Fe3+ - Wei Song; Mu Li; Sen Xu; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Wenhui Qiu; Zhihong Wang; Qi Song; Kalpana Bhatt; Caixia Fu (Environmental Pollution, 2023)

Model development and validation of personal exposure to PM2.5 among urban elders - Wei-Ting Hsu; Chun-Hung Ku; Mu-Jean Chen; Chih-Da Wu; Shih-Chun Candice Lung; Yu-Cheng Chen (Environmental Pollution, 2023)

Exploring the organic solvent resistance of anion exchange membranes based on poly(2,6-dimethyl-1,4-phenyl oxide) for electrodialysis desalination - Junbin Liao; Jingwen Xu; Huimin Ruan; Junjie Mu; Xu Jie; Wei Li; Yanqing Xu; Jiangnan Shen (Desalination, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Neural Mechanism Underlying Task-Specific Enhancement of Motor Learning by Concurrent Transcranial Direct Current Stimulation - Ying Wang; Jixian Wang; Qing-Fang Zhang; Ke-Wei Xiao; Liang Wang; Qing-Ping Yu; Qing Xie; Mu-Ming Poo; Yunqing Wen (Neuroscience Bulletin, 2023)

A multi-vortex micromixer based on the synergy of acoustics and inertia for nanoparticle synthesis - Yuwen Lu; Wei Tan; Shuoshuo Mu; Guorui Zhu (Analytica Chimica Acta, 2023)

From morphological to ecological adaptation of the cornea in Oxudercinae fishes - Wenxian Hu; Yuan Mu; Chuanyu Wei; Yulin Gai; Jie Zhang (Frontiers in Marine Science, 2022)
The outer cornea plays an important role in animal adaptation and survival in different environments. however, research on the morphological and ecological adaptation of corneal structure in amphibious fishes is limited. In this study, scanning electron microscopy (SEM) was used to evaluate the microstructure and adaptation of corneal epithelial cells in Oxudercinae. The results showed that the corneas of Oxudercinae species possess microridges, microvilli, and microplicae, as well as different numbers of epithelial cells. The morphological structure of corneal epithelial cells, observed by collecting samples and comparing the results with previous results, also showed different adaptive characteristics for moving between water and land. Further analyses revealed significant differences in epithelial cell density (F 4, 22 = 5.436, P=0.003) and microridge width (F 4, 22 = 8.392, P<0.001) among species with different levels of aquatic dependence. In addition, significant negative correlations of epithelial cell density with microridge width and separation width were confirmed (P<0.05). Interestingly, significant negative correlations of habitat type with cell density and microridges were uncovered, as well as a positive correlation between habitat type and separation width (P<0.05). The results indicated that the corneal structure of Oxudercinae species has characteristics of adaptation to an amphibious lifestyle.

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

miR-182-5p Delivered by Plasma Exosomes Promotes Sevoflurane-Induced Neuroinflammation and Cognitive Dysfunction in Aged Rats with Postoperative Cognitive Dysfunction by Targeting Brain-Derived Neurotrophic Factor and Activating NF-κB Pathway - Fu-sheng Wei; Mu-wen Rao; Yuan-lu Huang; Shi-biao Chen; Yu-qian Wu; Lei Yang (Neurotoxicity Research, 2022)

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

Efficient degradation of semi-coking wastewater in three-dimensional electro-Fenton by CuFe2O4 heterocatalyst - Wen-wen Gao; Ting Su; Wei Zhao; Zhi-fang Zhang; Miao Mu; Yong-hui Song; Xue-xue Zhang; Xin-yu Liu (Environmental Science and Pollution Research, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Residual analysis of QoI fungicides in multiple (six) types of aquatic organisms by UPLC-MS/MS under acutely toxic conditions - Hong Li; Shuai Hu; Fengshou Sun; Qi Sun; Ning Wang; Beixing Li; Nan Zou; Jin Lin; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Several major issues concerning the environmental transmission and risk prevention of SARS-CoV-2 - Jin Ma; Jian Xu; Xiaoli Zhao; Shouliang Huo; Xiaoli Duan; Yunsong Mu; Ying Wang; Yuan Wei; Jiang Chang; Xiaowei Jin; Fengchang Wu (Science China Earth Sciences, 2022)

Wood decay fungi: an analysis of worldwide research - Tong Li; Lizhen Cui; Xiufang Song; Xiaoyong Cui; Yulian Wei; Li Tang; Yanhong Mu; Zhihong Xu (Journal of Soils and Sediments, 2022)
Purpose Wood decay fungi are the only forms of life capable of degrading wood to its initial constituents, greatly contributing to the soil ecosystem. This study summarizes the current research status and development characteristics of global wood decay fungi research, in order to better understand their role in soils. Methods A bibliometric analysis was applied to the literature from 1913 to 2020, based on data from the Web of Science (WOS) Core Collection. For this, various bibliometric analysis methods, R (Biblioshiny package), and VOSviewer were applied. Results A total of 8089 documents in this field were identified in the WOS Core Collection. The annual number of publications tended to increase, with exponential growth after 2008. Researchers in this field were mainly concentrated in North Europe, the USA, and China. Biotechnology, applied microbiology, environmental sciences, and microbiology were the most popular WOS categories. Bioresource Technology and Applied Environmental Microbiology were the top two journals with the most citations. The top three authors with the most published papers were Dai YC, Martinez AT, and Cui BK. Co-occurrence analysis of author keywords identified six clusters, mainly divided into three categories: the classification and diversity, the degradation mechanisms, and the ecological functions of wood decay fungi. Clustering results further showed that the lignin degradation process and the application of wood decay fungi in industrial production and soil contamination remediation are current research hotspots. Conclusions We present a comprehensive and systematic overview of research related to wood decay fungi and provide a deep perspective to understand the associated research progress. This is important for facilitating the development of a profound understanding of the contribution of wood decay fungi to soil systems and the degradation of soil contaminants.

Validamycin reduces the transmission of Tomato chlorotic virus by Bemisia tabaci - Yang Mu; Xiaobin Shi; Zhuo Zhang; Zhanhong Zhang; Tianqi Wang; Yanqi Wang; Yan Wei; Xuguo Zhou; Min Xiang; Yong Liu; Deyong Zhang (Journal of Pest Science, 2022)

Duplex droplet digital PCR method for the detection of Enterocytozoon hepatopenaei and Vibrio parahaemolyticus acute hepatopancreatic necrosis disease - Huang Zhang; Han‐Yue Gong; Wei‐Wei Cao; Mu‐Yi Que; Lei Ye; Lei Shi (Journal of Fish Diseases, 2022)
Enterocytozoon hepatopenaei (EHP) and Vibrio parahaemolyticus acute hepatopancreatic necrosis disease (VPAHPND) are two of the diseases that have frequently infected farmed shrimp in recent years, causing great economic losses to the shrimp industry worldwide. In this study, we established a sensitive and accurate duplex droplet digital PCR (ddPCR) method that can simultaneously detect and quantify the two pathogens simultaneously. The results showed that the ddPCR methods could detect EHP and VPAHPND specifically. The sensitivity levels of ddPCR for EHP and VPAHPND were 2.3 copies/μl and 4.6 copies/μl, respectively, which were 10‐fold higher than the sensitivity of the qPCR assay and showed good reproducibility. Twenty‐six suspected diseased shrimp samples were used for practical determination. For EHP, the detection rates of ddPCR and qPCR were 53.84% and 42.31%, respectively; for VPAHPND, the detection rates of ddPCR and qPCR were both 23.08%. The results indicated that the ddPCR method shows superiority for detection in samples with low viral loads, which will facilitate monitoring of the source and transmission of EHP and VPAHPND and will help control shrimp epidemic disease.

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

Exploring sustainable solutions for the water environment in Chinese and Southeast Asian cities - Pingping Luo; Yong Mu; Shuangtao Wang; Wei Zhu; Binaya Kumar Mishra; Aidi Huo; Meimei Zhou; Jiqiang Lyu; Maochuan Hu; Weili Duan; Bin He; Daniel Nover (Ambio, 2022)

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

Analysis of the microseismicity characteristics in landslide dam failure flume tests: implications for early warning and dynamics inversion - Yunpeng Yang; Guan Chen; Xingmin Meng; Shiqiang Bian; Yan Chong; Wei Shi; Wanyu Jiang; Jiacheng Jin; Chen Li; Xinliang Mu; Dongxia Yue (Landslides, 2022)

IgE Reactivity of Potential Allergens from the Swimming Crab Portunus trituberculatus and the Research of ELISA Reagent for Detecting Crab Food Anaphylaxis - Xueni Qiu; Qiongyan Zhou; Xiaoxia Zhu; Wei Lin; Changkao Mu; Ronghua Li; Yangfang Ye; Weiwei Song; Ce Shi; Lei Liu; Huan Wang; Chunlin Wang; et al. (Journal of Ocean University of China, 2022)

A framework of analytical methods for horizontal behaviours of monopiles under V-H-M loads in sand - Linlong Mu; Wei Chen; Yiming Zhang; Xiaoxiang Chen; Wan Li (Marine Georesources & Geotechnology, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Simultaneous detection of ten kinds of insecticide residues in honey and pollen using UPLC-MS/MS with graphene and carbon nanotubes as adsorption and purification materials - Xiuyu Pang; Chenyu Li; Chuanjiang Zang; Lei Guan; Peng Zhang; Chunxiang Di; Nan Zou; Beixing Li; Wei Mu; Jin Lin (Environmental Science and Pollution Research, 2022)

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

Classification of electrocardiogram signals with waveform morphological analysis and support vector machines - Hongqiang Li; Zhixuan An; Shasha Zuo; Wei Zhu; Lu Cao; Yuxin Mu; Wenchao Song; Quanhua Mao; Zhen Zhang; Enbang Li; Juan Daniel Prades García (Medical & Biological Engineering & Computing, 2022)

Stability analysis of check dam impacted by intermittent surge - Daochuan Liu; Yong You; Jinfeng Liu; Qi Mu; Jin Feng; Lei Zhang; Anhui Wei; Huafu Tan (Bulletin of Engineering Geology and the Environment, 2022)

Cytotoxic benzopyranone and xanthone derivatives from a coral symbiotic fungus Cladosporium halotolerans GXIMD 02502 - Chao-Nan Wang; Hu-Mu Lu; Cheng-Hai Gao; Lang Guo; Zhen-Yu Zhan; Jun-Jian Wang; Yong-Hong Liu; Song-Tao Xiang; Jian Wang; Xiao-Wei Luo (Natural Product Research, 2021)

A landslide in Heifangtai, northwest of the Chinese Loess Plateau: triggered factors, movement characteristics, and failure mechanism - Jia-xu Kong; Jian-qi Zhuang; Jie-wei Zhan; Zheng-wei Bai; Yan-qiu Leng; Peng-hui Ma; Jian-bing Peng; Zuo-peng Wang; Tian-feng Gu; Jia-xing Sun; Fan-chen Zhang; Yuan-jun Xu; et al. (Landslides, 2021)

Correction to: Analysis of Microbial Diversity and Community Structure of Peanut Pod and Its Surrounding Soil in Peanut Rot Epidemic Area - Meijing He; Weiming Sun; Shunli Cui; Guojun Mu; Lifeng Liu; Wei Guo (Current Microbiology, 2021)

Expression and functional analysis of cytoplasmic dynein during spermatogenesis in Portunus trituberculatus - Chao-Guang Wei; Dan-Li Mu; Dao-Jun Tang; Jun-Quan Zhu; Cong-Cong Hou (Cell and Tissue Research, 2021)

Detecting Regional Deep Ocean Warming below 2000 meter Based on Altimetry, GRACE, Argo, and CTD Data - Yuanyuan Yang; Min Zhong; Wei Feng; Dapeng Mu (Advances in Atmospheric Sciences, 2021)

The impact of outward foreign direct investment on green innovation: the threshold effect of environmental regulation - Lihua Dai; Xiuru Mu; Chien-Chiang Lee; Wei Liu (Environmental Science and Pollution Research, 2021)

Clinical characteristics of re-hospitalized COVID-19 patients with recurrent positive SARS-CoV-2 RNA: a retrospective study - Lei Pan; Runsheng Wang; Na Yu; Chao Hu; Junhong Yan; Xiaomin Zhang; Tao Wang; Jungui Hao; Fuquan Gao; Tonggang Liu; Jing Wang; Xiaojing Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Markers of oxidative stress and toxicant exposure among young waterpipe smokers in the USA - Rime Jebai; Mohammad Ebrahimi Kalan; Mayra Vargas-Rivera; Olatokunbo Osibogun; Wei Li; Prem Gautam; Mu-Rong Chao; Chiung-Wen Hu; Zoran Bursac; Wasim Maziak (Environmental Science and Pollution Research, 2021)

Analysis of Microbial Diversity and Community Structure of Peanut Pod and Its Surrounding Soil in Peanut Rot Epidemic Area - Meijing He; Weiming Sun; Shunli Cui; Guojun Mu; Lifeng Liu; Wei Guo (Current Microbiology, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Synchronized research on endothelial dysfunction and microcirculation structure in dorsal skin of rats with type 2 diabetes mellitus - Yajie Wei; Huimin Chen; Qingzhuo Chi; Ying He; Lizhong Mu; Chao Liu; Yunxia Lu (Medical & Biological Engineering & Computing, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Dissipation kinetics and safety evaluation of pyraclostrobin and its desmethoxy metabolite BF 500-3 in a cucumber greenhouse agroecosystem - Lifei He; Falin He; Song Yang; Yangyang Gao; Beixing Li; Feng Liu; Wei Mu (Environmental Science and Pollution Research, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Freeze-thaw resistance of eco-material stabilized loess - Guo-yu Li; Xin Hou; Yu Zhou; Wei Ma; Yan-hu Mu; Dun Chen; Li-yun Tang (Journal of Mountain Science, 2021)

NO oxidation performance and kinetics analysis of BaMO3 (M=Mn, Co) perovskite catalysts - Ran Ao; Liping Ma; Zhiying Guo; Jing Yang; Liusen Mu; Jie Yang; Yi Wei (Environmental Science and Pollution Research, 2021)

QTL mapping and validation of bread wheat flag leaf morphology across multiple environments in different genetic backgrounds - Yang Tu; Hang Liu; Jiajun Liu; Huaping Tang; Yang Mu; Mei Deng; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2021)

A plant virus mediates interspecific competition between its insect vectors in Capsicuum annuum - Yong Chen; Xue Zheng; Hui Wei; Yong-Dui Chen; Kuan-Yu Zheng; Ye Mu; Xing-Yue Zhao; Li-Hua Zhao; Yu-Lin Gao; Li-Min Zheng; Jie Zhang (Journal of Pest Science, 2021)

The gut bacterial flora associated with brown planthopper is affected by host rice varieties - Zheng-Liang Wang; Hai-bo Pan; Wei Wu; Mu-Yu Li; Xiao-Ping Yu (Archives of Microbiology, 2021)

A novel, validated, and plant height-independent QTL for spike extension length is associated with yield-related traits in wheat - Cong Li; Huaping Tang; Wei Luo; Xuemei Zhang; Yang Mu; Mei Deng; Yaxi Liu; Qiantao Jiang; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2020)

Relationships among cigarette smoking, urinary biomarkers, and urothelial carcinoma risk: a case-control study - Chi-Jung Chung; Hui-Tsung Hsu; Chao-Hsiang Chang; Sheng-Wei Li; Chiu-Shong Liu; Mu-Chi Chung; Guo-Wei Wu; Wei-Ting Jung; Yen-Jung Kuo; Hui-Ling Lee (Environmental Science and Pollution Research, 2020)

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

A novel, major, and validated QTL for the effective tiller number located on chromosome arm 1BL in bread wheat - Jiajun Liu; Huaping Tang; Xiangru Qu; Hang Liu; Cong Li; Yang Tu; Shuiqing Li; Ahsan Habib; Yang Mu; Shoufeng Dai; Mei Deng; Qiantao Jiang; et al. (Plant Molecular Biology, 2020)

The effects of inhibiting the activation of hepatic stellate cells by lignan components from the fruits of Schisandra chinensis and the mechanism of schisanhenol - Xiaoli He; Jiamei Chen; Yongping Mu; Hua Zhang; Gaofeng Chen; Ping Liu; Wei Liu (Journal of Natural Medicines, 2020)

Efficacy of fluopyram as a candidate trunk-injection agent against Bursaphelenchus xylophilus - Guangying Liu; Xu Lin; Shuangyu Xu; Guang Liu; Zhenyu Liu; Feng Liu; Wei Mu (European Journal of Plant Pathology, 2020)

Constrained optimization model of the volume of initial rainwater storage tank based on ANN and PSO - Shengnan He; Wenxue Chen; Xiangpeng Mu; Wei Cui (Environmental Science and Pollution Research, 2020)

Effects of the 1BL/1RS translocation on 24 traits in a recombinant inbred line population - Hang Liu; Huaping Tang; Puyang Ding; Yang Mu; Ahsan Habib; Yaxi Liu; Qiantao Jiang; Guoyue Chen; Houyang Kang; Yuming Wei; Youliang Zheng; Xiujin Lan; et al. (Cereal Research Communications, 2020)

Identification and characterization of mRNAs and lncRNAs of a barley shrunken endosperm mutant using RNA-seq - Yaya Zou; Huaping Tang; Ting Li; Min Sun; Xiangru Qu; Jieguang Zhou; Congcong Yang; Yang Mu; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Guangdeng Chen; et al. (Genetica, 2020)

Impacts of replacement of dietary fish oil by vegetable oils on growth performance, anti-oxidative capacity, and inflammatory response in large yellow croaker Larimichthys crocea - Hua Mu; Chaoqing Wei; Yanjiao Zhang; Huihui Zhou; Ying Pan; Jia Chen; Wenbing Zhang; Kangsen Mai (Fish Physiology and Biochemistry, 2020)

Sublethal effects of anthranilic diamide insecticides on the demographic fitness and consumption rates of the Coccinella septempunctata (Coleoptera: Coccinellidae) fed on Aphis craccivora - Jiangong Jiang; Yao Wang; Wei Mu; Zhengqun Zhang (Environmental Science and Pollution Research, 2020)

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

Correction to: Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2020)

Flag leaf size and posture of bread wheat: genetic dissection, QTL validation and their relationships with yield-related traits - Jian Ma; Yang Tu; Jing Zhu; Wei Luo; Hang Liu; Cong Li; Shuiqin Li; Jiajun Liu; Puyang Ding; Ahsan Habib; Yang Mu; Huaping Tang; et al. (Theoretical and Applied Genetics, 2020)

Nonlinear optimal moisture perturbations as excitation of primary MJO events in a hybrid coupled climate model - Yuntao Wei; Hong-Li Ren; Mu Mu; Joshua-Xiouhua Fu (Climate Dynamics, 2020)
Although the moisture feedback has been well known to be essential in the Madden–Julian Oscillation (MJO) dynamics, whether its pre-moistening effect plays a key role in exciting the onset of primary MJO events, as has been confirmed in the successive initiation, remains elusive. In this study, using a hybrid coupled climate model that has a good fidelity in simulating the intraseasonal variability, we develop a new framework of methodology to investigate the nonlinear excitation of primary MJO event, of which the key achievement is the successful implementation of the conditional nonlinear optimal perturbation (CNOP). In an application of this new framework, the CNOP-type moisture perturbations are calculated for the pre-chosen non-MJO reference states and generally favor a moistening in the equatorial region while drying in the poleward. Comparisons of the model simulation with observation give credibility to the existence of moisture signals several weeks before some primary MJO events. A suite of numerical experiments confirms that the CNOPs of moisture can contribute to the excitation and propagation of strong primary MJO events while random perturbations cannot. The moisture budget analysis further reveals the central importance of the horizontal moisture advection, especially the nonlinearly upscaled moisture transports associated with the high-frequency disturbances on the quasi-3–4-day and 6–8-day synoptic time scales, in supporting the nonlinear excitation of the primary MJO events. The subgrid-scale processes of evaporation, condensation and eddy transport of moisture are found to be critical for the pre-moistening effect in the boundary layer as well. This study directly supports the vital importance of the moisture perturbations, which are characterized by a particular pattern concentrated at low levels, to the nonlinear growth and propagation of the primary MJO events.

Recent advances in Levansucrase and Inulosucrase: evolution, characteristics, and application - Wei Xu; Dawei Ni; Wenli Zhang; Cuie Guang; Tao Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2019)

Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Association between occupational exposure to trichloroethylene and serum levels of microRNAs: a cross-sectional molecular epidemiology study in China - Kyoung-Mu Lee; Bryan A. Bassig; Luoping Zhang; Roel C. Vermeulen; Wei Hu; Jason Y. Y. Wong; Chuangyi Qiu; Cuiju Wen; Yongshun Huang; Mark P. Purdue; Bu-Tian Ji; Laiyu Li; et al. (International Archives of Occupational and Environmental Health, 2019)

Engineering properties of loess stabilized by a type of eco-material, calcium lignosulfonate - Guo-yu Li; Xin Hou; Yan-hu Mu; Wei Ma; Fei Wang; Yu Zhou; Yun-cheng Mao (Arabian Journal of Geosciences, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Groove structure of porous hydroxyapatite scaffolds (HAS) modulates immune environment via regulating macrophages and subsequently enhances osteogenesis - Chenglong Li; Lu Yang; Xiaohua Ren; Mu Lin; Xiliang Jiang; Daonan Shen; Taotao Xu; Jing Ren; Lijuan Huang; Wei Qing; Jiajun Zheng; Yandong Mu (JBIC Journal of Biological Inorganic Chemistry, 2019)

Measurement of urinary arsenic profiles and DNA hypomethylation in a case–control study of urothelial carcinoma - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Han Chang; Chiu-Shong Liu; Wei-Ting Jung; Huei-Ju Liu; Saou-Hsing Liou; Mu-Chi Chung; Yu-Mei Hsueh (Archives of Toxicology, 2019)

MAOA-VNTR Genotype Effects on Ventral Striatum-Hippocampus Network in Alzheimer’s Disease: Analysis Using Structural Covariance Network and Correlation with Neurobehavior Performance - Hsin-I Chang; Ya-Ting Chang; Shih-Jen Tsai; Chi-Wei Huang; Shih-Wei Hsu; Mu-En Liu; Wen-Neng Chang; Chia-Yi Lien; Shu-Hua Huang; Chen-Chang Lee; Chiung-Chih Chang (Molecular Neurobiology, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Regulation of flowering time via miR172-mediated APETALA2-like expression in ornamental gloxinia (Sinningia speciosa) - Xiao-yan Li; Fu Guo; Sheng-yun Ma; Mu-yuan Zhu; Wei-huai Pan; Hong-wu Bian (Journal of Zhejiang University-SCIENCE B, 2019)

Pedobacter pollutisoli sp. nov., Isolated from Tetrabromobisphenol A-Contaminated Soil - Yang Mu; Zhuang Ke; Chen-Xi Feng; Xiao-Wei Wang; Xiao-Wen Wang; Hong-Mei Wang; Qing Chen; Jian He (Current Microbiology, 2019)

Emergency Control Scheme for Upstream Pools of Long‐Distance Canals - Wei Cui; Xiangpeng Mu; Wenxue Chen; T.A. Stephens; B.P. Bledsoe (Irrigation and Drainage, 2019)
An emergency control scheme is proposed for pools upstream of a canal experiencing flow obstruction incidents. In order to achieve a prompt and efficient transition process, operation strategies are set out. It is suggested to switch from a constant downstream depth operation method to a constant volume operation method under qualified conditions. Based on a balanced pool operation equation and a transitional time estimation equation, a two‐step gate operation method is designed, which is compatible with the operation method of constant downstream depth and the mixed pool operation method of constant downstream depth and constant volume. The emergency control scheme is tested by simulations on the 561 km long Middle Route Project (MPR) of the South‐to‐North Water Diversion Project in China consisting of 30 pools. The constant downstream depth and mixed pool operation methods are examined. Results indicate that the control scheme operates well under the emergency situation of a flow obstruction incident. Canal flow moves promptly and effectively to the new steady state by switching to the constant volume method. Back and forth volume variation is avoided and a significant improvement is obtained in terms of transition time, while the times of check gate operation remain roughly the same. © 2018 John Wiley & Sons, Ltd.

Tilapia fisheries in Guangdong Province, China: Socio‐economic benefits, and threats on native ecosystems and economics - Dang En Gu; Fan Dong Yu; Ye Xin Yang; Meng Xu; Hui Wei; Du Luo; Xi Dong Mu; Yin Chang Hu (Fisheries Management and Ecology, 2019)
Tilapia is one of the groups of fish species most widely cultured globally. China has been the largest producer of tilapia in the world since 1990s. Guangdong Province produces almost 40% of all tilapia in China because of its suitable geography and weather conditions, and tilapia culture has brought considerable economic benefits. Unfortunately, many of the biological traits that make tilapia popular for culture also contribute to its success as an invader. Tilapia has invaded natural waters and has become the dominant fish in many rivers of Guangdong Province, causing economic loss in capture fisheries, and affecting native fish species, biodiversity and aquatic ecosystems. Poor fishery management, water quality degradation and biodiversity loss have all facilitated the tilapia invasion. Tilapia have filled the niches left vacant by now locally extinct native species resulting from environmental changes in freshwater ecosystems of the province. The introduction of tilapia has both advantages and disadvantages, which should be managed to use effectively the various tilapia species in aquaculture while controlling their spread in natural waters.

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Permafrost warming along the Mo’he-Jiagedaqi section of the China-Russia crude oil pipeline - Fei Wang; Guo-yu Li; Wei Ma; Yun-cheng Mao; Yan-hu Mu; Mihaela Serban; Yong-jun Cai (Journal of Mountain Science, 2019)

Permian integrative stratigraphy and timescale of China - Shuzhong Shen; Hua Zhang; Yichun Zhang; Dongxun Yuan; Bo Chen; Weihong He; Lin Mu; Wei Lin; Wenqian Wang; Jun Chen; Qiong Wu; Changqun Cao; et al. (Science China Earth Sciences, 2019)

Efficiency of sequential UV/H2O2 and biofilm process for the treatment of secondary effluent - Peng-Fei Yan; Shoujun Yuan; Wei Wang; Zhen-Hu Hu; Yang Mu; Han-Qing Yu (Environmental Science and Pollution Research, 2019)

A 55 K SNP array-based genetic map and its utilization in QTL mapping for productive tiller number in common wheat - Jiajun Liu; Wei Luo; Nana Qin; Puyang Ding; Han Zhang; Congcong Yang; Yang Mu; Huaping Tang; Yaxi Liu; Wei Li; Qiantao Jiang; Guoyue Chen; et al. (Theoretical and Applied Genetics, 2018)

Human activity during the late Pleistocene in the Lop Nur region, northwest China: Evidence from a buried stone artifact - Kangkang Li; Xiaoguang Qin; Xiaoyan Yang; Bing Xu; Lei Zhang; Guijin Mu; Dong Wei; Chunxue Wang; Yong Wu; Xiaohong Tian; Yongchong Lin; Wen Li; et al. (Science China Earth Sciences, 2018)

Baseline sensitivity of Phytophthora capsici to the strobilurin fungicide benzothiostrobin and the efficacy of this fungicide - Dicheng Ma; Jiamei Zhu; Leiming He; Kaidi Cui; Wei Mu; Feng Liu (European Journal of Plant Pathology, 2018)

Hoeflea prorocentri sp. nov., isolated from a culture of the marine dinoflagellate Prorocentrum mexicanum PM01 - Qiao Yang; Zhi-Wei Jiang; Cheng-Hui Huang; Ruo-Nan Zhang; Ling-Zhi Li; Guang Yang; Li-Juan Feng; Guang-Feng Yang; Heng Zhang; Xiao-Ling Zhang; Jun Mu (Antonie van Leeuwenhoek, 2018)

Favorable compatibility of nitenpyram with the aphid predator, Coccinella septempunctata L. (Coleoptera: Coccinellidae) - Jiangong Jiang; Dicheng Ma; Zhengqun Zhang; Caihong Yu; Feng Liu; Wei Mu (Environmental Science and Pollution Research, 2018)

Catechol-O-Methyltransferase Val158Met Polymorphism on Striatum Structural Covariance Networks in Alzheimer’s Disease - Chiung-Chih Chang; Shih-Jen Tsai; Nai-Ching Chen; Chi-Wei Huang; Shih-Wei Hsu; Ya-Ting Chang; Mu-En Liu; Wen-Neng Chang; Wan-Chen Tsai; Chen-Chang Lee (Molecular Neurobiology, 2018)

Planetary scale selection of the Madden–Julian Oscillation in an air-sea coupled dynamic moisture model - Yuntao Wei; Fei Liu; Mu Mu; Hong-Li Ren (Climate Dynamics, 2018)

Characteristics of thawed interlayer and its effect on embankment settlement along the Qinghai-Tibet Railway in permafrost regions - Zhi-zhong Sun; Wei Ma; Shu-juan Zhang; Yan-hu Mu; Han-bo Yun; Hong-lei Wang (Journal of Mountain Science, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Assessment of the baseline sensitivity and resistance risk of Colletotrichum acutatum to fludioxonil - Yangyang Gao; Lifei He; Wei Mu; Beixing Li; Jin Lin; Feng Liu (European Journal of Plant Pathology, 2018)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Fish invasion in the river systems of Guangdong Province, South China: Possible indicators of their success - D. E. Gu; Y. C. Hu; M. Xu; H. Wei; D. Luo; Y. X. Yang; F. D. Yu; X. D. Mu (Fisheries Management and Ecology, 2018)
Although a large number of fish species have been introduced into Guangdong Province in Southern China, a few species, such as tilapia ( Tilapia spp.), North African catfish Clarias gariepinus Burchell, mrigal carp, Cirrhinus mrigala (Bloch) and the sucker mouth catfish ( Hypostomus sp.), have established natural populations and can be considered “successful invaders” in large rivers. The specific mechanisms underlying these contrasting results among different introduced fish species remain understudied. The relationship between multiple abiotic–biotic factors and the success of four invasive species was investigated using survey data for the Guangdong Province river ecosystem. In contrast to previous studies that have considered species‐specific traits, the focus was on economic, ecological and anthropogenic factors to predict invasion success. Four main predictive indicators were found: (1) successful invaders were of low or no commercial value; (2) successful invaders tolerated a wide range of environmental conditions, including poor water quality; (3) biodiversity loss accelerated the growth of non‐native populations; (4) human disturbance facilitated population growth and spread of invasive fish species. To lessen the impacts of invasive fish species, the selection of breeding species and breeding areas, maintenance of water quality and reduction in water pollution, protection of the diversity of fish species and reduction of human interference should be addressed.

Sensitivity of Colletotrichum acutatum to six fungicides and reduction in incidence and severity of chili anthracnose using pyraclostrobin - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Australasian Plant Pathology, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

First detection of enteric adenoviruses genotype 41 in recreation spring areas of Taiwan - Yi-Jia Shih; Chi-Wei Tao; Hsin-Chi Tsai; Wen-Chien Huang; Tung-Yi Huang; Jung-Sheng Chen; Yi-Chou Chiu; Tsui-Kang Hsu; Bing-Mu Hsu (Environmental Science and Pollution Research, 2017)

The potential of fludioxonil for anthracnose control on China chili fruit - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Phytoparasitica, 2017)

Effects of intercropping tea with aromatic plants on population dynamics of arthropods in Chinese tea plantations - Zhengqun Zhang; Chao Zhou; Yongyu Xu; Xiaoqin Huang; Lixia Zhang; Wei Mu (Journal of Pest Science, 2017)

Effects of freeze-thaw cycle on engineering properties of loess used as road fills in seasonally frozen ground regions, North China - Guo-yu Li; Wei Ma; Yan-hu Mu; Fei Wang; Shan-zhi Fan; Ya-hu Wu (Journal of Mountain Science, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

Baseline sensitivity and control efficacy of antibiosis fungicide tetramycin against Botrytis cinerea - Yingying Song; Leiming He; Lele Chen; Yupeng Ren; Hongbao Lu; Su Geng; Wei Mu; Feng Liu (European Journal of Plant Pathology, 2016)

Genome-wide analysis of shoot growth-associated alternative splicing in moso bamboo - Long Li; Tao Hu; Xueping Li; Shaohua Mu; Zhanchao Cheng; Wei Ge; Jian Gao (Molecular Genetics and Genomics, 2016)

Improving of lipid productivity of the biodiesel promising green microalga Chlorella pyrenoidosa via low-energy ion implantation - Renjie Tu; Wenbiao Jin; Mu Wang; Songfang Han; Abd El-Fatah Abomohra; Wei-Min Wu (Journal of Applied Phycology, 2016)

Identification of potential cargo proteins of transportin protein AtTRN1 in Arabidopsis thaliana - Bo Yan; Xiaoning Wang; Zhenyu Wang; Ni Chen; Changjun Mu; Kaili Mao; Lirong Han; Wei Zhang; Heng Liu (Plant Cell Reports, 2016)

Sublethal concentration of benzothiazole adversely affect development, reproduction and longevity of Bradysia odoriphaga (Diptera: Sciaridae) - Yunhe Zhao; Peng Zhang; Yongbiao Zhai; Chengyu Chen; Qiuhong Wang; Jingkun Han; Zhengqun Zhang; Feng Liu; Wei Mu (Phytoparasitica, 2016)

Alteration of cytochrome P450 1 regulation and HSP 70 level in brain of juvenile common carp (Cyprinus carpio) after chronic exposure to tributyltin - Zhi-Hua Li; Li-Qiao Zhong; Yan-Hua Wu; Wei-Na Mu (Fish Physiology and Biochemistry, 2016)

Seasonal difference of human adenoviruses in a subtropical river basin based on 1-year monthly survey - Chi-Wei Tao; Bing-Mu Hsu; Po-Min Kao; Wen-Chien Huang; Tsui-Kang Hsu; Ying-Ning Ho; Yen-Ju Lu; Cheng-Wei Fan (Environmental Science and Pollution Research, 2016)

Baseline sensitivity and efficacy of the sterol biosynthesis inhibitor triflumizole against Botrytis cinerea - Yingying Song; Datong Xu; Hongbao Lu; Leiming He; Lele Chen; Junan Shao; Chunmei Xu; Wei Mu; Feng Liu (Australasian Plant Pathology, 2016)

Effects of inefficient transcription termination of rbcL on the expression of accD in plastids of Arabidopsis thaliana - Baoye He; Ying Mu; Wei Chi (Photosynthesis Research, 2015)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Characterization of the Aggregation-Induced Enhanced Emission of N,N′-bis(4-methoxysalicylide)benzene-1,4-diamine - Fuyong Wu; Guangjun Xu; Xi Zeng; Lan Mu; Carl Redshaw; Gang Wei (Journal of Fluorescence, 2015)

Laboratory testing on heat transfer of frozen soil blocks used as backfills of pile foundation in permafrost along Qinghai-Tibet electrical transmission line - Guoyu Li; Qihao Yu; Wei Ma; Yanhu Mu; Xingbai Li; Zhaoyu Chen (Arabian Journal of Geosciences, 2015)

Catalpol Inhibited the Proliferation of T24 Human Bladder Cancer Cells by Inducing Apoptosis Through the Blockade of Akt-Mediated Anti-apoptotic Signaling - Di Jin; Ming Cao; Xin Mu; Guoliang Yang; Wei Xue; Yiran Huang; Haige Chen (Cell Biochemistry and Biophysics, 2015)

Seasonal distribution of potentially pathogenic Acanthamoeba species from drinking water reservoirs in Taiwan - Po-Min Kao; Bing-Mu Hsu; Tsui-Kang Hsu; Jorn-Hon Liu; Hsiang-Yu Chang; Wen-Tsai Ji; Kai-Jiun Tzeng; Shih-Wei Huang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Comparison of Bradysia odoriphaga Yang and Zhang reared on artificial diet and different host plants based on an age-stage, two-sex life table - Peng Zhang; Feng Liu; Wei Mu; Qiuhong Wang; Hui Li (Phytoparasitica, 2015)

Degradation characteristics of permafrost under the effect of climate warming and engineering disturbance along the Qinghai–Tibet Highway - Hui Peng; Wei Ma; Yan-hu Mu; Long Jin; Kun Yuan (Natural Hazards, 2015)

A Potential Association Between Antibiotic Abuse and Existence of Related Resistance Genes in Different Aquatic Environments - Chao-Yu Hsu; Bing-Mu Hsu; Wen-Tsai Ji; Tien-Yu Chang; Po-Min Kao; Shao-Feng Tseng; Tsung-Yu Shen; Feng-Cheng Shih; Cheng-Wei Fan; Jorn-Hon Liu (Water, Air, & Soil Pollution, 2015)

Resistance mechanisms and risk assessment regarding indoxacarb in the beet armyworm, Spodoptera exigua - Ming Gao; Wei Mu; Wei Wang; Chao Zhou; Xiuhuan Li (Phytoparasitica, 2014)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Expression screening and annotation of Sepiella maindroni ink sac cDNA library - WEI-WEI SONG; CHANG-KAO MU; SHAO CHU; YU-YU ZHANG; PING-PING ZHAN; CHUN-LIN WANG (Journal of Genetics, 2014)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

CANAL CONTROLLER FOR THE LARGEST WATER TRANSFER PROJECT IN CHINA - Wei Cui; Wenxue Chen; Xiangpeng Mu; Yinbaoligao Bai (Irrigation and Drainage, 2014)
A control system consisting of a decentralized feedback controller, a centralized feedforward controller and a decoupler is presented for the Middle Route Project for South‐to‐North Water Transfer in China. The feedback controller is a kind of level‐discharge cascade adaptive PI controller, which has the merit of diminishing unknown disturbances and reducing coupling effects of the control action on downstream canal pools. The volume compensation algorithm is used in the feedforward controller to reduce time delays in scheduled delivery of the long‐ distance canal system. And the decoupler is designed to decrease the coupling effects of the control action from the upstream pools. This controller is tested in part of the Middle Route Project for South‐to‐North Water Transfer using distant downstream water depth by means of numerical simulation. The results show that the control system can efficiently deal with known and unknown disturbances, and can significantly reduce the delay time and the coupling effects between the canal pools. Copyright © 2013 John Wiley & Sons, Ltd.

Overexpression of a dominant-negative mutant of SIRT1 in mouse heart causes cardiomyocyte apoptosis and early-onset heart failure - WenLi Mu; QingJun Zhang; XiaoQiang Tang; WenYan Fu; Wei Zheng; YunBiao Lu; HongLiang Li; YuSheng Wei; Li Li; ZhiGang She; HouZao Chen; DePei Liu (Science China Life Sciences, 2014)

Spectrum analysis of wind profiling radar measurements - Zheng Ruan; Ruiqi Mu; Ming Wei; Runsheng Ge (Journal of Meteorological Research, 2014)

Grassland coverage inter-annual variation and its coupling relation with hydrothermal factors in China during 1982–2010 - Wei Zhou; Chengcheng Gang; Yizhao Chen; Shaojie Mu; Zhengguo Sun; Jianlong Li (Journal of Geographical Sciences, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Gene cloning, expression and characterisation of a new β-agarase, AgWH50C, producing neoagarobiose from Agarivorans gilvus WH0801 - Nan Liu; Xiangzhao Mao; Meng Yang; Bozhong Mu; Dongzhi Wei (World Journal of Microbiology and Biotechnology, 2014)

The relationship between chemical elements in soil and whole blood, and fluorosis induced by coal-fired pollution - Hao Wang; Lihong Mu; Miao Jiang; Yingxiong Wang; Wei Yan; Yongzhuo Jiao (Environmental Monitoring and Assessment, 2014)

Identification of microRNA-18a as a novel regulator of the insulin-like growth factor-1 in the proliferation and regeneration of deer antler - Wei Hu; Ting Li; Lei Wu; Mu Li; Xingyu Meng (Biotechnology Letters, 2014)

Apoptosis repressor with caspase recruitment domain is regulated by MAPK/PI3K and confers drug resistance and survival advantage to AML - P. Y. Mak; D. H. Mak; H. Mu; Y. Shi; P. Ruvolo; V. Ruvolo; R. Jacamo; J. K. Burks; W. Wei; X. Huang; S. M. Kornblau; M. Andreeff; et al. (Apoptosis, 2014)

Cloning and expression analysis of Foxl2 during the reproductive cycle in Korean rockfish, Sebastes schlegeli - Wei J. Mu; Hai S. Wen; Ji F. Li; Feng He (Fish Physiology and Biochemistry, 2013)

Global detection of large lunar craters based on the CE-1 digital elevation model - Lei Luo; Lingli Mu; Xinyuan Wang; Chao Li; Wei Ji; Jinjin Zhao; Heng Cai (Frontiers of Earth Science, 2013)

Whole exome sequencing identifies mutation of EDNRA involved in ACTH-independent macronodular adrenal hyperplasia - Jie Zhu; Liang Cui; Wei Wang; Xing-Yi Hang; A-Xiang Xu; Su-Xia Yang; Jing-Tao Dou; Yi-Ming Mu; Xu Zhang; Jiang-Ping Gao (Familial Cancer, 2013)

Lignin Pyrolysis Components and Upgrading—Technology Review - Wei Mu; Haoxi Ben; Art Ragauskas; Yulin Deng (BioEnergy Research, 2013)

Cratering process and morphological features of the Xiuyan impact crater in Northeast China - XinYuan Wang; Lei Luo; HuaDong Guo; LingLi Mu; Chao Li; Wei Ji; Heng Cai (Science China Earth Sciences, 2013)

Development and characterization of EST-derived microsatellite makers for swimming crab, Portunus trituberculatus - Qian Wei; Chunlin Wang; Changkao Mu; Weiwei Song; Ronghua Li (Conservation Genetics Resources, 2013)

Cloning and expression analysis of follicle-stimulating hormone and luteinizing hormone receptor during the reproductive cycle in Korean rockfish (Sebastes schlegeli) - Wei J. Mu; Hai S. Wen; Feng He; Ji F. Li; Miao Liu; Yuan Q. Zhang; Jian Hu; Bao X. Qi (Fish Physiology and Biochemistry, 2013)

Spatio-temporal dynamics of vegetation coverage and its relationship with climate factors in Inner Mongolia, China - Shaojie Mu; Hongfei Yang; Jianlong Li; Yizhao Chen; Chengcheng Gang; Wei Zhou; Weimin Ju (Journal of Geographical Sciences, 2013)

An Arabidopsis mutant atcsr-2 exhibits high cadmium stress sensitivity involved in the restriction of H2S emission - Ya-wei Li; Ze-hua Gong; Yao Mu; Yi-xian Zhang; Zeng-jie Qiao; Li-ping Zhang; Zhu-ping Jin; Hua Li; Yan-xi Pei (Journal of Zhejiang University-SCIENCE B, 2012)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

Isolation and functional analysis of Thmfs1, the first major facilitator superfamily transporter from the biocontrol fungus Trichoderma harzianum - Mu Liu; Jun Liu; Wei Min Wang (Biotechnology Letters, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Molecular detection and comparison of Acanthamoeba genotypes in different functions of watersheds in Taiwan - Po-Min Kao; Bing-Mu Hsu; Nai-Hsiung Chen; Kuan-Hao Huang; Chin-Chun Huang; Dar-Der Ji; Jung-Sheng Chen; Wei-Chen Lin; Shih-Wei Huang; Yi-Chou Chiu (Environmental Monitoring and Assessment, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

Mechanistic insights into the link between visfatin gene C-1535T polymorphism and coronary artery disease: an in vitro study - Yong-Sheng Wang; Wei Gao; Hong-Fen Li; Ze-Mu Wang; Jun Zhu; Huan Zhao; Jian-Jun Yan; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular and Cellular Biochemistry, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

High-level expression of the Penicillium notatum glucose oxidase gene in Pichia pastoris using codon optimization - Zhaowei Gao; Zhuofu Li; Yuhong Zhang; Huoqing Huang; Mu Li; Liwei Zhou; Yunming Tang; Bin Yao; Wei Zhang (Biotechnology Letters, 2012)

Resistance of Spodoptera exigua to ten insecticides in Shandong, China - Chao Zhou; Yongqiang Liu; Weili Yu; Zhaorong Deng; Ming Gao; Feng Liu; Wei Mu (Phytoparasitica, 2011)

Improved efficiency of separate hexose and pentose fermentation from steam-exploded corn stalk for butanol production using Clostridium beijerinckii - Xindong Mu; Wei Sun; Chao Liu; Haisong Wang (Biotechnology Letters, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Alternative splicing of the antitrypsin gene in the silkworm, Bombyx mori - Hui-fen Liu; Yi-nü Li; Ru Jia; Wei-zheng Cui; Zhi-mei Mu; Zhi-fang Zhang (Molecular Biology Reports, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Utilization of polymerase chain reaction and selective media cultivation to identify Legionella in Taiwan spring water samples - Shih-Wei Huang; Bing-Mu Hsu; Chin-Chun Huang; Jung-Sheng Chen (Environmental Monitoring and Assessment, 2011)

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Triaxial ellipsoid models of the Moon based on the laser altimetry data of Chang’E-1 - WenRui Wang; Fei Li; JianJun Liu; Xin Ren; XiaoDuan Zou; LingLi Mu; JianGuo Yan; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Convective scale structure and evolution of a squall line observed by C-band dual Doppler radar in an arid region of northwestern China - Liping Liu; Wei Zhuang; Pengfei Zhang; Rong Mu (Advances in Atmospheric Sciences, 2010)

Efficiency of methods applied for goat estrous synchronization in subtropical monsoonal climate zone of Southwest China - Yongju Zhao; Jiahua Zhang; Hong Wei; Xinming Sun; Biao Mu; Mingju Yu; Lingbing Wang (Tropical Animal Health and Production, 2010)

The effective expression of xylanase gene in Candida utilis by 18S rDNA targeted homologous recombination in pGLR9K - Wang Wei; Yang Hong-Lan; Bao HuiFang; Zhang Daoyuan; Shan Qi-mu-ge; Andrew J. Wood (Molecular Biology Reports, 2010)

Immune response to fused core protein of hepatitis C virus and truncated tetanus toxin peptides in mice - Xing-bin Hu; Qiao-hong Yue; Hai-feng Ouyang; Yao-zhen Chen; Xue-qing Xu; Wen Yin; San-hua Wei; Xian-qing Zhang; Shi-jie Mu (Archives of Virology, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Copper affects biofilm inductiveness to larval settlement of the serpulid polychaete Hydroides elegans (Haswell) - Wei-Yang Bao; On-On Lee; Hong-Chun Chung; Mu Li; Pei-Yuan Qian (Biofouling, 2010)

Heavy metal induced ecological risk in the city of Urumqi, NW China - Binggan Wei; Fengqing Jiang; Xuemei Li; Shuyong Mu (Environmental Monitoring and Assessment, 2010)

Differences in Action of PACAP-27 and PACAP-38 on Guinea Pig Gallbladder Smooth Muscle Using Synthetic C-terminally Modified PACAP Peptides - Mu-xin Wei; Satoru Naruse; Tsuyoshi Ozaki; Ping Hu; Victor Wray; Kiyoshi Nokihara (International Journal of Peptide Research and Therapeutics, 2009)

Lipopolysaccharide upregulates uPA, MMP-2 and MMP-9 via ERK1/2 signaling in H9c2 cardiomyoblast cells - Yi-Chang Cheng; Li-Mien Chen; Mu-Hsin Chang; Wei-Kung Chen; Fuu-Jen Tsai; Chang-Hai Tsai; Tung-Yuan Lai; Wei-Wen Kuo; Chih-Yang Huang; Chung-Jung Liu (Molecular and Cellular Biochemistry, 2009)

Spectroscopic Study of 2-(2-pyridyliminomethyl)phenol as a Novel Fluorescent Probe for Superoxide Anion Radicals and Superoxide Dismutase Activity - Shuhui Ma; Wei Mu; Jigang Gao; Jie Zhou (Journal of Fluorescence, 2009)

Lessons from comparative physiology: could uric acid represent a physiologic alarm signal gone awry in western society? - Richard J. Johnson; Yuri Y. Sautin; William J. Oliver; Carlos Roncal; Wei Mu; L. Gabriela Sanchez-Lozada; Bernardo Rodriguez-Iturbe; Takahiko Nakagawa; Steven A. Benner (Journal of Comparative Physiology B, 2009)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Molecular cloning and characterisation of a non-TIR-NBS-LRR type disease resistance gene analogue from sugarcane - Q. You-Xiong; L. Jian-Wei; Z. Ji-Sen; R. Miao-Hong; X. Li-Ping; Z. Mu-Qing (Sugar Tech, 2008)

Efficient organogenesis and plantlet regeneration in the timber species Cunninghamia lanceolata (Lamb.) Hook - Mu-lan Zhu; Ji Wang; Yang Yu; Sheng-jun Liu; Zhi-ming Wei (In Vitro Cellular & Developmental Biology - Plant, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Microbial production of 1,3-propanediol by Klebsiella pneumoniae using crude glycerol from biodiesel preparations - Ying Mu; Hu Teng; Dai-Jia Zhang; Wei Wang; Zhi-Long Xiu (Biotechnology Letters, 2006)

Pharmacokinetic study with N-Ile1-Thr2-63-desulfato-r-hirudin in rabbits by means of bioassay - Guo-zhu Han; Hong-can Ren; Yong Lu; Ying Li; Shu Xiao; Hong-wei Ye; He-mu Wang (Journal of Zhejiang University-SCIENCE B, 2006)

The role of earthworms (Eisenia fetida) in influencing bioavailability of heavy metals in soils - Bei Wen; Xiao-yu Hu; Ying Liu; Wei-sheng Wang; Mu-hua Feng; Xiao-quan Shan (Biology and Fertility of Soils, 2004)

Plant regeneration from in vitro -cultured seedling leaf protoplasts of Actinidia eriantha Benth - Y.-J. Zhang; Y.-Q. Qian; X.-J. Mu; Q.-G. Cai; Y.-L. Zhou; X.-P. Wei (Plant Cell Reports, 1998)